Prepolymer having a triazine skeleton, composition containing the same, method for forming a resist pattern, method for forming a circuit pattern, and method for purifying the prepolymer

By reacting multifunctional cyanate with phenolic compounds to form triazine framework prepolymers, the pattern control problem of low molecular weight photoresist materials in fine processing is solved, and the preparation of high resolution and low roughness of photolithographic patterns and optical components is achieved.

JP7627431B2Active Publication Date: 2025-02-06MITSUBISHI GAS CHEM CO INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021522314
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-30
Filing Date
2020-05-22
Publication Date
2025-02-06
Estimated Expiration
2040-05-22

AI Technical Summary

Technical Problem

In the prior art, low molecular weight photoresist materials are difficult to control the pattern size during fine processing, resulting in large pattern surface roughness, limiting the further development of fine refinement, and traditional triazine compounds are difficult to control the molecular weight during the treatment process, resulting in difficult processing.

Method used

By reacting the multifunctional cyanate compound with a phenolic compound to form a prepolymer with a triazine framework, a prepolymer with medium molecular weight was prepared, which not only maintains good thermal stability but is easy to dissolve in the solvent, and avoids high-temperature curing treatment.

Benefits of technology

High resolution, low roughness lithographic pattern formation is achieved, pattern control capability is improved, and material processing is simplified, suitable for lithography and optical components preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627431000001
    Figure 0007627431000001
  • Figure 0007627431000002
    Figure 0007627431000002
  • Figure 0007627431000003
    Figure 0007627431000003
Patent Text Reader

Abstract

A prepolymer having a triazine skeleton, which is formed by reacting a multifunctional cyanate compound and a phenol with each other. The multifunctional cyanate compound is preferably represented by formula (1) or (2). The prepolymer is especially useful as a film forming material for lithography. In the formulae, X represents an oxygen atom or the like; R2 represents a single bond or a divalent group having 0-40 carbon atoms, which may contain a heteroatom; R3 represents a trivalent group having 0-40 carbon atoms, which may contain a heteroatom; each of R0 independently represents an optionally substituted alkyl group having 0-40 carbon atoms, or the like; each m independently represents an integer of 0-9; and each p independently represents an integer of 0-3.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a prepolymer having a triazine skeleton, a composition containing the same, a method for forming a resist pattern, a method for forming a circuit pattern, and a method for purifying the prepolymer. [Background technology]

[0002] In the manufacture of semiconductor devices, microfabrication is carried out by lithography using photoresist materials, but in recent years, with the increasing integration and speed of LSI (large-scale integrated circuits), there is a demand for even finer pattern rules. In addition, the light source for lithography used in forming resist patterns has been shortened from KrF excimer lasers (248 nm) to ArF excimer lasers (193 nm), and the introduction of extreme ultraviolet light (EUV, 13.5 nm) is also expected.

[0003] However, in lithography using conventional polymer resist materials, the molecular weight is large, about 10,000 to 100,000, and the molecular weight distribution is wide, so that roughness occurs on the pattern surface, making it difficult to control the pattern dimensions, and there is a limit to miniaturization. Therefore, various low molecular weight resist materials have been proposed so far in order to give resist patterns with higher resolution. Since low molecular weight resist materials have small molecular sizes, it is expected to give resist patterns with high resolution and small roughness.

[0004] Currently, various low molecular weight resist materials are known. For example, an alkali-developable negative radiation-sensitive composition using a low molecular weight polynuclear polyphenol compound as a main component (see, for example, Patent Document 1 and Patent Document 2) has been proposed, and an alkali-developable negative radiation-sensitive composition using a low molecular weight cyclic polyphenol compound as a main component (see, for example, Patent Document 3 and Non-Patent Document 1) has also been proposed as a candidate for a low molecular weight resist material having high heat resistance. In addition, it is known that a polyphenol compound, as a base compound of a resist material, can impart high heat resistance despite its low molecular weight, and is useful for improving the resolution and roughness of a resist pattern (see, for example, Non-Patent Document 2).

[0005] The present inventors have also proposed a resist composition containing a compound of a specific structure and an organic solvent as a material that has excellent etching resistance, is soluble in a solvent, and is applicable to a wet process (see Patent Document 4).

[0006] In addition to the above, cyanate compounds are known as compounds that can provide materials with high heat resistance despite their low molecular weight. Cyanate compounds cure to form triazine rings, giving cured products with excellent heat resistance. However, cyanate compounds are generally highly crystalline and have low solubility in solvents, making them difficult to handle. Up until now, attempts have been made to polymerize cyanate compounds to a low degree to produce compounds with an appropriate molecular weight and improve their ease of handling. However, the triazine reaction proceeds rapidly, making it extremely difficult to adjust the molecular weight, and it has not been easy to obtain compounds with an appropriate molecular weight. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2005-326838 A [Patent Document 2] JP 2008-145539 A [Patent Document 3] JP 2009-173623 A [Patent Document 4] International Publication No. 2013 / 024778 [Non-patent literature]

[0008] [Non-Patent Document 1] T.Nakayama,M.Nomura,K.Haga,M.Ueda:Bull.Chem.Soc.Jpn.,71,2979(1998) [Non-Patent Document 2] Shinji Okazaki and 22 others, "New Developments in Photoresist Material Development," CMC Publishing Co., Ltd., September 2009, pp. 211-259 Summary of the Invention [Problem to be solved by the invention]

[0009] In view of the above circumstances, an object of the present invention is to provide a prepolymer having excellent heat resistance and handleability. [Means for solving the problem]

[0010] The inventors have found that a prepolymer obtained by reacting a polyfunctional cyanate compound with a phenol can solve the above problems. That is, the present invention is as follows. [1] A prepolymer having a triazine skeleton formed by reacting a polyfunctional cyanate compound with a phenol. [2] The prepolymer according to [1], wherein the polyfunctional cyanate compound is represented by the following formula (1) or formula (2). [3] The prepolymer according to [1], wherein the polyfunctional cyanate compound is represented by the formula (3) described below. [4] The prepolymer according to any one of [1] to [3], wherein the phenol is represented by the formula (4) described below. [5] The prepolymer according to [1], [2], or [4], wherein the polyfunctional cyanate compound represented by the formula (1) is represented by the formula (1-1) described below. [6] The prepolymer according to [1], [2], or [4], wherein the polyfunctional cyanate compound represented by the formula (2) is represented by the formula (2-1) described below. [7] The prepolymer according to any one of [4] to [6], wherein the phenol represented by the formula (4) is a monophenol represented by the following formula (4-1) described later. [8] The prepolymer according to any one of [1] to [7], having a mass average molecular weight of 400 to 10,000. [9] The prepolymer according to any one of [1] to [8], which has a terminal phenolic hydroxyl group.

[10] A composition comprising the prepolymer according to any one of the above [1] to [9].

[11] The composition according to

[10] , further comprising a solvent.

[12] A resist film formed from the composition according to

[10] or

[11] .

[13] forming a resist film on a substrate using the composition according to

[10] or

[11] ; exposing at least a portion of the formed resist film; developing the exposed resist film to form a resist pattern; A method for forming a resist pattern comprising the steps of:

[14] A radiation-sensitive composition comprising the prepolymer according to any one of [1] to [9], a diazonaphthoquinone photoactive compound, and a solvent, The radiation-sensitive composition, wherein the content of the solvent in the composition is 20 to 99 mass %.

[15] When the components other than the solvent are considered to be solid contents, the solid contents are 1 to 99% by mass of the prepolymer; 99 to 1% by mass of the diazonaphthoquinone photoactive compound; and 0 to 49 mass % of other optional components.

[16] An amorphous film obtained by spin-coating the radiation-sensitive composition according to

[14] or

[15] .

[17] A method for producing an amorphous film, comprising a step of forming an amorphous film on a substrate using the radiation-sensitive composition according to any one of

[14] to

[16] .

[18] forming a resist film on a substrate using the radiation-sensitive composition according to any one of

[14] to

[16] ; exposing at least a portion of the formed resist film; developing the exposed resist film to form a resist pattern.

[19] An underlayer film for lithography formed from the composition according to

[10] or

[11] .

[20]

[10] or

[11] . A method for producing an underlayer film for lithography, comprising the step of forming an underlayer film on a substrate using the composition according to

[10] or

[11] . [twenty one] forming an underlayer film on a substrate using the composition according to

[10] or

[11] ; forming at least one photoresist layer on the underlayer film; irradiating predetermined areas of the photoresist layer with radiation and developing the photoresist layer to form a resist pattern; The method for forming a resist pattern comprises the steps of: [twenty two] forming an underlayer film on a substrate using the composition according to

[10] or

[11] ; forming an intermediate layer film on the underlayer film using a resist intermediate layer film material containing silicon atoms; forming at least one photoresist layer on the intermediate layer film; irradiating predetermined areas of the photoresist layer with radiation and developing the photoresist layer to form a resist pattern; a step of etching the intermediate layer film using the resist pattern as a mask to form an intermediate layer film pattern; forming an underlayer film pattern by etching the underlayer film using the intermediate layer film pattern as an etching mask; Etching the substrate using the underlayer film pattern as an etching mask to form a pattern on the substrate; The pattern forming method comprises the steps of: [twenty three] An optical component formed from the composition according to

[10] or

[11] . Effect of the Invention

[0011] The present invention can provide a prepolymer having excellent heat resistance and handleability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention provides a prepolymer having a triazine skeleton, which is particularly useful as a film-forming material for lithography or a material for forming optical components, a composition containing the prepolymer, a method for forming a resist pattern, a method for forming an insulating film, a method for forming a circuit pattern, and a method for purifying the prepolymer. The present invention will be described in detail below. In the present invention, "X to Y" includes the end values ​​X and Y.

[0013] 1. Prepolymers with triazine structures The prepolymer having a triazine skeleton of the present invention (hereinafter also referred to as the "prepolymer of the present invention") is a kind of triazine compound obtained by reacting a polyfunctional cyanate compound with a phenol. The prepolymer of the present invention is a polymer having a flowability that is lightly polymerized and is generally called B-stage in the field of thermosetting resins.

[0014] When phenols are added as catalysts to cyanate compounds and resins and reacted in various solvents, triazine rings are formed while three-dimensionalization progresses, and the cyanate compounds and resins can be made high molecular weight while maintaining solubility in the solvent. The added phenols are involved in triazine cyclization and are incorporated into the resulting polymer, so that the polymer (prepolymer) has a terminal hydroxyl group and a triazine ring, and therefore can achieve both heat resistance and solubility. In conventional technology, it was necessary to form heat-resistant triazine rings by curing them with high temperature heating, but in the present invention, a polymer having a triazine ring can be obtained without high temperature heating.

[0015] In the application of resist films or lithography underlayer films, the time during which high-temperature baking can be performed is limited in the formation method, and it is therefore useful to obtain a polymer having a triazine ring in advance.

[0016] The prepolymer of the present invention has molecular chains extending three-dimensionally, so it is difficult to express it by a general formula. The prepolymer of the present invention has, for example, the following structure.

[0017] [ka]

[0018] In the above formula, Cy is a moiety derived from a polyfunctional cyanate compound, and Ph is a moiety derived from a phenol.

[0019] [Multifunctional cyanate compounds] A polyfunctional cyanate compound is a compound having a plurality of cyanate groups. In the present invention, the polyfunctional cyanate compound is preferably a bifunctional, branched trifunctional, or linear polyfunctional (three or more functional) type. Each type will be described below.

[0020] 1) Difunctional cyanate compounds The difunctional cyanate compound is preferably represented by formula (1).

[0021] [ka]

[0022] In the formula, each cyanate group is bonded to an aromatic group. X represents an oxygen atom, a sulfur atom, a single bond, or no cross-linking. When X represents no cross-linking, it means that there is no bond represented by -X-. In terms of availability of raw materials, X may be no cross-linking.

[0023] R 2 is a divalent group having 0 to 40 carbon atoms which may contain a single bond or a heteroatom. A heteroatom is an atom other than a hydrogen atom or a carbon atom, and examples of the heteroatom include an oxygen atom, a nitrogen atom, a sulfur atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, and a silicon atom. From the viewpoint of availability of raw materials, a sulfur atom, an oxygen atom, a nitrogen atom, or a silicon atom is preferred. Therefore, R 2 When a heteroatom is contained, the group may be an oxygen atom, a sulfur atom, a carbonyl group, a carboxy group (-C(=O)O-), a carboxy group-containing group, a carbonyl dioxide group (-OC(=O)O-), a sulfonyl group (-SO2-), an amide group (-C(=O)-NH-), or -(Si(R)2-O-). h Examples of such groups include a --containing group (R is an alkyl group having 1 to 2 carbon atoms, and h is a number from 1 to 100), a hexafluoroisopropylidene group, a phthalidodiyl group, and a group derived by removing a hydrogen atom from a hydroxyl group of an aryldiol.

[0024] Also, R 2 If does not contain heteroatoms, R 2 is a divalent hydrocarbon group having 1 to 40 carbon atoms. Examples of such a hydrocarbon group include linear, branched, or cyclic alkylene groups having 1 to 40 carbon atoms, and aralkylene groups having 6 to 40 carbon atoms.

[0025] Examples of the alkylene group include linear alkylene groups such as a methylene group or an ethylene group, branched alkylene groups such as an isopropylidene group, and cyclic alkylene groups such as a cyclohexylene group or an adamantanediyl group. The alkylene group may be substituted with a halogen atom.

[0026] Examples of the aralkylene group include a benzylene group, a fluorenediyl group, etc. The aromatic ring in the aralkylene group may be a heterocycle, and these rings may have an alkyl group having 1 to 4 carbon atoms or a halogen atom as a substituent.

[0027] In formula (1), R 0 represents an alkyl group having 1 to 40 carbon atoms which may have a substituent, an aryl group having 6 to 40 carbon atoms which may have a substituent, an alkenyl group having 2 to 40 carbon atoms which may have a substituent, an alkynyl group having 2 to 40 carbon atoms which may have a substituent, an alkoxy group having 1 to 40 carbon atoms which may have a substituent, or an aryloxy group having 6 to 40 carbon atoms which may have a substituent.

[0028] The alkyl group may be linear, branched or cyclic, and examples thereof include methyl, ethyl, n-propyl, i-propyl, n-butyl, i-butyl, t-butyl, cyclopropyl, and cyclobutyl groups. These groups may have a halogen atom, a nitro group, an amino group, a thiol group, a hydroxyl group, or a group in which the hydrogen atom of a hydroxyl group is substituted with a dissociable group, as a substituent. Hereinafter, these substituents are also referred to as "specific substituents".

[0029] Examples of the aryl group include a phenyl group, a naphthalene group, a biphenyl group, etc. The specific substituent may be bonded to these groups.

[0030] Examples of the alkenyl group include a propenyl group, a butenyl group, etc. The specific substituent may be bonded to these groups.

[0031] Examples of the alkynyl group include a propynyl group, a butynyl group, etc. The specific substituent may be bonded to these groups.

[0032] Examples of the alkoxy group include a methoxy group, an ethoxy group, a propoxy group, a cyclohexyloxy group, etc. The specific substituent may be bonded to these groups.

[0033] Examples of the aryloxy group include a phenoxy group, a naphthaleneoxy group, a biphenyloxy group, etc. The specific substituent may be bonded to these groups.

[0034] The dissociable group refers to a group that dissociates in the presence or absence of a catalyst, and among them, a group that can be cleaved in the presence of an acid to generate an alkali-soluble group is called an acid-dissociable group. Examples of the alkali-soluble group include, but are not limited to, a phenolic hydroxyl group, a carboxyl group, a sulfonic acid group, a hexafluoroisopropanol group, and the like. Among them, from the viewpoint of the availability of an introduction reagent, a phenolic hydroxyl group or a carboxyl group is preferred, and a phenolic hydroxyl group is particularly preferred. The dissociable group preferably has a property of undergoing a chain cleavage reaction in the presence of an acid in order to enable high-sensitivity and high-resolution pattern formation. The dissociable group is not particularly limited, and can be appropriately selected from those proposed in, for example, hydroxystyrene resins and (meth)acrylic acid resins used in chemically amplified resist compositions for KrF and ArF. Preferred examples of the acid-dissociable group include groups that have the property of being dissociated by acid and are selected from the group consisting of a 1-substituted ethyl group, a 1-substituted-n-propyl group, a 1-branched alkyl group, a silyl group, an acyl group, a 1-substituted alkoxymethyl group, a cyclic ether group, an alkoxycarbonyl group, and an alkoxycarbonylalkyl group.

[0035] m is R 0Each p represents the number of groups, and each p is independently an integer of 0 to 9, preferably 0 to 8, more preferably 0 to 2, and still more preferably 0. p represents the number of condensed rings of the aromatic group, and each p is independently an integer of 0 to 3, preferably 0 to 2, and more preferably 0.

[0036] Formula (1) is preferably represented by formula (1-1). In this formula, m' is an integer of 0 to 8, preferably 0 or 1, and more preferably 0. R 2 ,p,is defined as above.

[0037] [ka]

[0038] An example of the cyanate compound represented by formula (1) is shown below.

[0039] [ka]

[0040] [ka]

[0041] 2) Branched trifunctional cyanate compound The branched trifunctional cyanate compound is preferably represented by formula (2). In the formula, X, R 0 , p and m have the same meanings as X in formula (1).

[0042] [ka]

[0043] In the formula, the cyanate groups are bonded to the aromatic groups one by one. 3is a trivalent group having 0 to 40 carbon atoms which may contain a heteroatom. The heteroatom is as described above. The trivalent group having 0 to 40 carbon atoms may contain a double bond, but is preferably a group derived by removing three hydrogen atoms from an alkyl group. Examples of such groups include alkylidyne groups such as a methylidyne group or an ethylidyne group. Further, examples of the trivalent group include aromatic groups derived by removing three hydrogen atoms from an aromatic ring.

[0044] Formula (2) is preferably represented by formula (2-1). In the formula, R 0 , p is defined as above, and m' is defined the same as m' in formula (1-1).

[0045] [ka]

[0046] An example of the cyanate compound represented by formula (2) is shown below.

[0047] [ka]

[0048] 3) Linear polyfunctional (three or more functional) cyanate compounds The linear polyfunctional cyanate compound is preferably represented by formula (3).

[0049] [ka]

[0050] In the formula, Ar 1 are each independently an aromatic group. An aromatic group is a group derived by removing a hydrogen atom from an aromatic compound, and examples of the aromatic compound include, but are not limited to, benzene, naphthalene, anthracene, biphenyl, etc. 1 may be different for each repeating unit, so that the cyanate compound may be a copolymer.

[0051] R a are each independently an alkyl group having 1 to 6 carbon atoms which may have a substituent, an aryl group having 6 to 12 carbon atoms which may have a substituent, an alkoxy group having 1 to 4 carbon atoms which may have a substituent, an aralkyl group in which an alkyl group having 1 to 6 carbon atoms which may have a substituent and an aryl group having 6 to 12 carbon atoms are bonded, or a phosphate group. The aryl group may have a substituent. r represents the number of cyanate groups and is each independently an integer of 0 to 3. a The numbers indicate the number of 1 The number of possible bonds of Ar - (r + 2). 1 The number of bonds that can be made is Ar 1 is the maximum number of substituents that can be attached when it exists as a compound rather than a group. For example, Ar 1 is 6 when it is a group derived from benzene, 8 when it is a group derived from naphthalene, and 10 when it is a group derived from biphenyl. t is the average repeat number and is in the range of 2 to 50. However, the total number of r is 3 or more.

[0052] R a The alkyl group in the formula (1) is 0 The carbon number of R is 1 to 6. a The aryl group in the formula (1) is 0 The carbon number of R is 6 to 12. a The alkoxy group in the formula (1) is R 0 The carbon number of R is 1 to 4. a The aralkyl group in the above formula (I) includes a group in which the above alkyl group and the above aryl group are bonded together.

[0053] When a plurality of D's are present, each D is independently a single bond or a divalent group having 0 to 50 carbon atoms which may have a heteroatom. The group may be a hydrocarbon group in which a hydrogen atom may be substituted with a heteroatom, a group containing 1 to 10 nitrogen atoms and at least one N atom is directly bonded to Ar. 1Examples of the divalent organic group bonded to D (for example, -N-R'-N- (wherein R' is a hydrocarbon group)), a carbonyl group (-CO-), a carboxy group (-C(=O)O-), a carbonyl dioxide group (-OC(=O)O-), a sulfonyl group (-SO2-), a divalent sulfur atom, or a divalent oxygen atom) include those bonded to D. D may also have a cyanate group as a substituent.

[0054] Specific examples of the hydrocarbon group in D include, but are not limited to, a methylene group, an ethylene group, a trimethylene group, a dimethylmethylene group, a cyclopentylene group, a cyclohexylene group, a trimethylcyclohexylene group, a biphenyldiyldimethylene group, a naphthalenediyldimethylene group, a (dimethyl)methylene-phenylene-(dimethyl)methylene group, a fluorenediyl group, a phthalidodiyl group, a benzylene group, a furanylmethylene group, an adamantanediyl group, etc. The hydrogen atom in the group may be substituted with a halogen atom such as a fluorine atom or a chlorine atom, an alkoxy group such as a methoxy group or a phenoxy group, a cyano group, etc.

[0055] Examples of the organic group containing a nitrogen atom in D include, but are not limited to, a group represented by -N-R'-N- (wherein R' represents a hydrocarbon group), an imino group, a polyimide group, and the like.

[0056] An example of the cyanate compound represented by formula (3) is shown below.

[0057] [ka]

[0058] [ka]

[0059] [ka]

[0060] [ka] (However, Ar 1 is a combination of two or more of the above groups.

[0061] [Phenols] The phenol refers to a compound having a phenolic hydroxyl group, and is preferably represented by formula (4). The phenol represented by formula (4) is a compound having at least one phenolic hydroxyl group in an aromatic ring.

[0062] [ka]

[0063] In the formula, Z is a single bond, a heteroatom, or a divalent hydrocarbon group having 1 to 40 carbon atoms which may contain a heteroatom. The heteroatom is as explained in formula (1). The divalent hydrocarbon group having 1 to 40 carbon atoms is also as explained in formula (1). From the viewpoint of ease of synthesis, etc., Z is preferably a single bond, a divalent heteroatom, or the above-mentioned linear, branched, or cyclic alkylene group having 1 to 40 carbon atoms, or an aralkylene group having 6 to 40 carbon atoms.

[0064] n indicates the number of repetitions and is an integer of 0 to 3, with 0 or 1 being preferred.

[0065] R 1 are each independently an optionally substituted alkyl group having 1 to 40 carbon atoms, an optionally substituted aryl group having 6 to 40 carbon atoms, an optionally substituted alkenyl group having 2 to 40 carbon atoms, an optionally substituted alkoxy group having 1 to 40 carbon atoms, a halogen atom, or a hydroxyl group, provided that R 1 At least one of the groups is a hydroxyl group. The aryl group, alkenyl group, and alkoxy group are as described in formula (1).

[0066] e is R 1and each independently represents an integer of 1 to 9, preferably 1 or 2. f represents the number of condensed rings in the aromatic group, and each independently represents an integer of 0 to 3, preferably 0 to 2, and more preferably 0.

[0067] The phenol represented by formula (4) is preferably a monophenol represented by formula (4-1). 1 , e, and f are defined as above, except that the number of hydroxyl groups is one.

[0068] [ka]

[0069] Specific examples of the phenols represented by formula (4) include monofunctional or bifunctional compounds such as phenol, cresol, xylenol, butylphenol, amylphenol, nonylphenol, bisphenol A, tetramethylbisphenol F, bisphenol F, bisphenol S, bisphenol K, biphenol, tetramethylbiphenol, hydroquinone, methylhydroquinone, dimethylhydroquinone, trimethylhydroquinone, di-tert-butylhydroquinone, resorcinol, methylresorcinol, catechol, methylcatechol, dihydroxynaphthalene, dihydroxymethylnaphthalene, and dihydroxydimethylnaphthalene; condensates of phenols or naphthols with aldehydes; condensates of phenols or naphthols with xylylene glycol; condensates of phenols or naphthols with bismethoxymethylbiphenyl; condensates of phenols with isopropenylacetophenone; and reaction products of phenols and dicyclopentadiene. These can be obtained by known methods.

[0070] Moreover, a compound represented by the formula (5) can also be used as the phenol.

[0071] [ka]

[0072] In the formula, each Y is independently an oxygen atom or a sulfur atom. 5 are each independently a 2w-valent hydrocarbon group having 1 to 30 carbon atoms. The hydrocarbon group may have a cyclic hydrocarbon group, a double bond, a hetero atom, or an aromatic group having 6 to 30 carbon atoms. w is an integer of 1 to 4. The 2w-valent hydrocarbon group is an alkylene group having 1 to 30 carbon atoms when w=1, an alkanetetrayl group having 1 to 30 carbon atoms when w=2, an alkanehexyl group having 2 to 30 carbon atoms when w=3, and an alkaneoctyl group having 3 to 30 carbon atoms when w=4. Examples of the 2w-valent hydrocarbon group include those having a linear, branched, or cyclic structure. The 2w-valent hydrocarbon group may have a cyclic hydrocarbon group, a double bond, a hetero atom, or an aromatic group having 6 to 30 carbon atoms. The cyclic hydrocarbon group also includes a bridged cyclic hydrocarbon group.

[0073] R 4 are each independently an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, or a hydroxyl group. 4 At least one of the alkyl groups is a hydroxyl group. 0 Among the alkyl groups described above, those having 1 to 10 carbon atoms can be mentioned. As the aryl group, R 0 Among the aryl groups described above, those having 6 to 10 carbon atoms can be mentioned. As the alkenyl group, R 0 Among the alkenyl groups described above, those having a carbon number of 2 to 10 can be mentioned. Each v is independently an integer of 1 to 6, and w is an integer of 1 to 4. Specifically, the compound represented by formula (5) can be a compound disclosed in Japanese Patent No. 5979384.

[0074] Furthermore, the compound represented by formula (6) can also be used as the phenol.

[0075] [ka]

[0076] In the formula, R 6 is a 2w-valent hydrocarbon group having 1 to 30 carbon atoms, R 7 ~R 10 are each independently an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 10 carbon atoms, an alkenyl group having 2 to 10 carbon atoms, or a hydroxyl group. 9 At least one of or R 10 At least one of the groups is a hydroxyl group. 7 and m 8 are each independently an integer of 0 to 8, 9 and m 10 are each independently an integer of 0 to 9, 9 and m 10 At least one of is an integer from 1 to 9. w is an integer from 1 to 4. p 7 ~p 10 are each independently an integer of 0 to 2. The 2w-valent hydrocarbon group, the alkyl group, the aryl group, the aryl group, and the alkenyl group are as described in formula (5). Specifically, the compound represented by formula (6) may be a compound disclosed in WO2015 / 137486.

[0077] [Synthesis conditions] Generally, as a curing catalyst for a cyanate compound, organic metal salts such as zinc octylate, copper octylate, manganese octylate, zinc naphthenate, copper naphthenate, manganese naphthenate, imidazoles such as 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, and derivatives such as adducts of carboxylic acids or acid anhydrides of these imidazoles are used. However, when the polyfunctional cyanate compound used in the present invention is reacted in an organic solvent using these catalysts, it becomes difficult to control the polymerization reaction rate, and precipitation occurs due to insolubilization caused by the rapid construction of a three-dimensional crosslinked structure accompanying cyclization trimerization. On the other hand, when a polyfunctional cyanate compound is reacted with a phenol in an organic solvent, three-dimensionalization proceeds while forming a triazine ring, and high molecular weight proceeds while maintaining solubility in the solvent, so that the triazine compound of the present invention is obtained. Phenols participate in this reaction as a catalyst and are incorporated into the compound produced, so they also function as reaction substrates.

[0078] [Reaction conditions] The prepolymer of the present invention is obtained by reacting the polyfunctional cyanate compound with a phenol. The compounding ratio of the two is not limited, but it is preferable to use 0.5 to 10 equivalents of the phenol relative to the polyfunctional cyanate compound, and more preferably 0.7 to 5.0 equivalents.

[0079] The reaction temperature is not limited, but in order to avoid a rapid reaction, it is preferably 10 to 80° C., more preferably 20 to 50° C. The reaction time is appropriately adjusted depending on the reaction temperature, but can be, for example, about 1 to 600 hours.

[0080] The reaction may be carried out without a solvent, but is preferably carried out in the presence of a solvent to avoid a rapid reaction. A known solvent may be used, but halogenated hydrocarbons such as methylene chloride and 1,2-dichloroethane are preferred. When a solvent is used, the raw material concentration in the reaction solution (the total concentration of the polyfunctional cyanate compound and phenols) is preferably 5 to 50% by mass, more preferably 20 to 40% by mass.

[0081] [Characteristics] The prepolymer of the present invention has excellent heat resistance because it has a triazine skeleton. Furthermore, the prepolymer of the present invention is soluble in various organic solvents (especially safe solvents) and is easy to handle. The molecular weight is not limited, but is preferably 400 to 10,000, more preferably 1,000 to 9,000, in terms of mass average molecular weight. In the present invention, the molecular weight is measured by GPC.

[0082] The prepolymer of the present invention has a phenolic hydroxyl group derived from a phenol or a cyanate compound, and further has a cyanate group derived from a polyfunctional cyanate compound, and therefore has curability. Therefore, it gives a cured product with excellent heat resistance and mechanical properties. From the viewpoint of curing reactivity, it is preferable that the phenolic hydroxyl group is present at the terminal of the prepolymer of the present invention. The prepolymer of the present invention may be crystalline or amorphous, but is preferably amorphous in consideration of solubility in a solvent.

[0083] [Application] The prepolymer of the present invention has excellent solubility in organic solvents (especially safe solvents) and is therefore useful as a film-forming material for lithography. The prepolymer of the present invention has a relatively high carbon concentration and a relatively low oxygen concentration, and therefore is useful as a lithography film that can suppress film deterioration during high-temperature baking and has excellent etching resistance to oxygen plasma etching and the like. The prepolymer of the present invention has a high refractive index due to its high aromatic ring density, and is therefore useful as an optical part having excellent transparency and being resistant to coloration even when heat-treated. These uses are described below.

[0084] 2. Composition The composition of the present invention contains the prepolymer. In addition to the prepolymer, the composition preferably contains a solvent, an acid generator, an acid diffusion controller, or a combination thereof. In the composition, the prepolymer is also referred to as component (A). As described above, the prepolymer of the present invention is useful as a film-forming composition for lithography for forming a film for lithography having excellent heat resistance and etching resistance. Specifically, the composition is useful for forming a photoresist film, an underlayer film for lithography, and a permanent resist film. The composition useful for forming a photoresist film is also referred to as a "resist composition."

[0085] [Resist composition] The resist composition preferably contains a solvent. The solvent is not particularly limited, but may be, for example, ethylene glycol monoalkyl ether acetates such as ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, ethylene glycol mono-n-propyl ether acetate, and ethylene glycol mono-n-butyl ether acetate; ethylene glycol monoalkyl ethers such as ethylene glycol monomethyl ether and ethylene glycol monoethyl ether; propylene glycol monoalkyl ether acetates such as propylene glycol monomethyl ether acetate (PGMEA), propylene glycol monoethyl ether acetate, propylene glycol mono-n-propyl ether acetate, and propylene glycol mono-n-butyl ether acetate; propylene glycol monoalkyl ethers such as propylene glycol monomethyl ether (PGME) and propylene glycol monoethyl ether; methyl lactate, ethyl lactate, n-propyl lactate, n-butyl lactate, and n-amyl lactate. Lactic acid esters such as methyl acetate, ethyl acetate, n-propyl acetate, n-butyl acetate, n-amyl acetate, n-hexyl acetate, methyl propionate, ethyl propionate, and other aliphatic carboxylic acid esters; methyl 3-methoxypropionate, ethyl 3-methoxypropionate, methyl 3-ethoxypropionate, ethyl 3-ethoxypropionate, methyl 3-methoxy-2-methylpropionate, 3-methoxybutyl acetate, 3-methyl-3-methoxybutyl acetate, 3-methoxy-3-methylpropionate. Examples of suitable solvents include, but are not limited to, other esters such as butyl ester, butyl 3-methoxy-3-methylbutyrate, methyl acetoacetate, methyl pyruvate, and ethyl pyruvate; aromatic hydrocarbons such as toluene and xylene; ketones such as 2-heptanone, 3-heptanone, 4-heptanone, cyclopentanone (CPN), and cyclohexanone (CHN); amides such as N,N-dimethylformamide, N-methylacetamide, N,N-dimethylacetamide, and N-methylpyrrolidone; and lactones such as γ-lactone. These solvents can be used alone or in combination of two or more.

[0086] The solvent is preferably a safe solvent, more preferably at least one selected from the group consisting of PGMEA, PGME, CHN, CPN, 2-heptanone, anisole, butyl acetate, ethyl propionate, and ethyl lactate, and even more preferably at least one selected from the group consisting of PGMEA, PGME, and CHN.

[0087] The amounts of solid components (components other than the solvent) and solvent in the resist composition are not particularly limited, but with respect to a total mass of 100% by mass of the solid components and the solvent, the amounts are preferably 1 to 80% by mass of solid components and 20 to 99% by mass of solvent, more preferably 1 to 50% by mass of solid components and 50 to 99% by mass of solvent, even more preferably 2 to 40% by mass of solid components and 60 to 98% by mass of solvent, and particularly preferably 2 to 10% by mass of solid components and 90 to 98% by mass of solvent.

[0088] The resist composition may contain the following components as necessary. 1) Acid generator (component (C)) The resist composition preferably contains one or more acid generators that generate acid directly or indirectly upon irradiation with any radiation selected from visible light, ultraviolet light, excimer laser, electron beam, extreme ultraviolet light (EUV), X-rays, and ion beams. The acid generator is not particularly limited, but for example, those described in International Publication No. 2013 / 024778 can be used. The acid generators can be used alone or in combination.

[0089] The amount of the acid generator is preferably 0.001 to 49% by mass, more preferably 1 to 40% by mass, even more preferably 3 to 30% by mass, and particularly preferably 10 to 25% by mass, based on the total mass of the solid components (100% by mass). With this amount of acid generator, a resist film can be obtained that can achieve a pattern profile with high sensitivity and low edge roughness. In processing the resist film, if an excimer laser is used instead of ultraviolet rays such as g-rays and i-rays, finer processing is possible, and if an electron beam, extreme ultraviolet rays, X-rays, or ion beams are used as high-energy rays, further finer processing is possible.

[0090] 2) Acid crosslinker (component (G)) The resist composition preferably contains one or more acid crosslinkers. The acid crosslinker is a compound capable of intramolecularly or intermolecularly crosslinking the component (A) in the presence of an acid generated from an acid generator. Examples of such acid crosslinkers include compounds having one or more groups (hereinafter referred to as "crosslinkable groups") capable of crosslinking the component (A).

[0091] Examples of such crosslinkable groups include, but are not limited to, (i) hydroxyalkyl groups such as hydroxy (C1-C6 alkyl groups), C1-C6 alkoxy (C1-C6 alkyl groups), and acetoxy (C1-C6 alkyl groups), or groups derived therefrom; (ii) carbonyl groups such as formyl and carboxy (C1-C6 alkyl groups), or groups derived therefrom; (iii) nitrogen-containing groups such as dimethylaminomethyl, diethylaminomethyl, dimethylolaminomethyl, diethylolaminomethyl, and morpholinomethyl groups; (iv) glycidyl group-containing groups such as glycidyl ether, glycidyl ester, and glycidylamino groups; (v) groups derived from aromatic groups such as C1-C6 allyloxy (C1-C6 alkyl groups), C1-C6 aralkyloxy (C1-C6 alkyl groups), such as benzyloxymethyl and benzoyloxymethyl groups; and (vi) polymerizable multiple bond-containing groups such as vinyl and isopropenyl groups. Among these, hydroxyalkyl groups and alkoxyalkyl groups are preferred, with alkoxymethyl groups being particularly preferred.

[0092] The acid crosslinking agent having a crosslinkable group is not limited, but for example, those described in International Publication No. 2013 / 024778 can be used. The acid crosslinking agents can be used alone or in combination of two or more.

[0093] The amount of the acid crosslinker is preferably 0.5 to 49% by mass, more preferably 0.5 to 40% by mass, further preferably 1 to 30% by mass, and particularly preferably 2 to 20% by mass, based on the total mass of the solid components (100% by mass). When the amount of the acid crosslinker is 0.5% by mass or more, the effect of suppressing the solubility of the resist film in an alkaline developer is improved, and the reduction in the residual film rate and the occurrence of swelling or meandering of the pattern can be suppressed. On the other hand, when the amount is 49% by mass or less, the reduction in the heat resistance of the resist can be suppressed.

[0094] 3) Acid diffusion controller (ingredient (E)) The resist composition may contain an acid diffusion control agent that has the effect of controlling the diffusion of the acid generated from the acid generator by radiation exposure in the resist film, thereby preventing undesirable chemical reactions in unexposed regions. Such an acid diffusion control agent improves the storage stability of the resist composition. In addition, the resolution is improved, and the line width change of the resist pattern due to the variation of the exposure time before radiation exposure and the exposure time after radiation exposure can be suppressed, so that the process stability is extremely high. Examples of such acid diffusion control agents include, but are not limited to, radiation decomposable basic compounds such as nitrogen atom-containing basic compounds, basic sulfonium compounds, and basic iodonium compounds.

[0095] The acid diffusion control agent is not particularly limited, and for example, those described in International Publication No. 2013 / 024778 can be used. The acid diffusion control agent can be used alone or in combination. The amount of the acid diffusion control agent is preferably 0.001 to 49% by mass, more preferably 0.01 to 10% by mass, still more preferably 0.01 to 5% by mass, and particularly preferably 0.01 to 3% by mass, based on the total mass of the solid components (100% by mass). The amount of the acid diffusion inhibitor can prevent a decrease in resolution, deterioration of the pattern shape, dimensional fidelity, and the like. Furthermore, even if the waiting time from electron beam irradiation to heating after radiation irradiation is long, the shape of the upper layer of the pattern can be prevented from being deteriorated. In addition, when the amount is 10% by mass or less, a decrease in sensitivity, developability of the unexposed part, and the like can be prevented. In addition, by using such an acid diffusion control agent, the storage stability of the resist composition is improved, and the resolution is further improved, and the line width change of the resist pattern due to the variation of the waiting time before radiation irradiation and the waiting time after radiation irradiation can be suppressed, and the process stability is extremely improved.

[0096] 4) Other components (component (F)) The resist composition can contain, as other component (F), one or more of the following: a dissolution promoter, a dissolution controller, a sensitizer, a surfactant, an oxoacid of an organic carboxylic acid or a derivative thereof, or a phosphorus oxoacid or a derivative thereof. i) Dissolution enhancer When the solubility of component (A) in the developer is too low, the dissolution promoter increases the solubility and appropriately increases the dissolution rate of component (A) during development. Examples of the dissolution promoter include low molecular weight phenolic compounds, such as bisphenols and tris(hydroxyphenyl)methane. These dissolution promoters can be used alone or in combination of two or more. The amount of the dissolution promoter is appropriately adjusted depending on the type of component (A) used, and is preferably 0 to 49% by mass, more preferably 0 to 5% by mass, even more preferably 0 to 1% by mass, and particularly preferably 0% by mass, based on 100% by mass of the total mass of the solid components.

[0097] ii) Dissolution Control Agents When the solubility of component (A) in the developer is too high, the dissolution controller controls the solubility and appropriately reduces the dissolution rate during development. Such a dissolution controller is preferably one that does not undergo chemical changes during the steps of baking, radiation exposure, development, etc. of the resist film. Examples of the dissolution controller include, but are not limited to, aromatic hydrocarbons such as phenanthrene, anthracene, and acenaphthene; ketones such as acetophenone, benzophenone, and phenyl naphthyl ketone; and sulfones such as methyl phenyl sulfone, diphenyl sulfone, and dinaphthyl sulfone. These dissolution controllers can be used alone or in combination. The amount of the dissolution controller is appropriately adjusted depending on the type of component (A) used, and is preferably 0 to 49% by mass, more preferably 0 to 5% by mass, even more preferably 0 to 1% by mass, and particularly preferably 0% by mass, based on the total mass of the solid components (100% by mass).

[0098] iii) Sensitizer The sensitizer absorbs the energy of the irradiated radiation and transfers the energy to the acid generator (component (C)), thereby increasing the amount of acid generated and improving the apparent sensitivity of the resist. Such sensitizers are not limited, but examples thereof include benzophenones, biacetyls, pyrenes, phenothiazines, and fluorenes. These sensitizers can be used alone or in combination of two or more. The amount of the sensitizer is appropriately adjusted depending on the type of component (A) used, but is preferably 0 to 49% by mass, more preferably 0 to 5% by mass, even more preferably 0 to 1% by mass, and particularly preferably 0% by mass, based on 100% by mass of the total mass of the solid components.

[0099] iv) Surfactants The surfactant improves the coatability and striation of the resist composition, the developability of the resist, etc. The surfactant may be any of anionic surfactants, cationic surfactants, nonionic surfactants, and amphoteric surfactants, but nonionic surfactants are preferred. Nonionic surfactants have good affinity with the solvent used in the production of the resist composition, and are more likely to exhibit their effects. Examples of nonionic surfactants include, but are not limited to, polyoxyethylene higher alkyl ethers, polyoxyethylene higher alkyl phenyl ethers, and higher fatty acid diesters of polyethylene glycol. Examples of commercially available products include, but are not limited to, trade names such as F-TOP (manufactured by GEMCO), Megafac (manufactured by Dainippon Ink and Chemicals), Fluorad (manufactured by Sumitomo 3M), Asahi Guard, Surflon (all manufactured by Asahi Glass Co., Ltd.), Pepol (manufactured by Toho Chemical Industry Co., Ltd.), KP (manufactured by Shin-Etsu Chemical Co., Ltd.), and Polyflow (manufactured by Kyoeisha Yushi Kagaku Kogyo Co., Ltd.). The amount of the surfactant is adjusted appropriately depending on the type of component (A) used, but is preferably 0 to 49 mass%, more preferably 0 to 5 mass%, even more preferably 0 to 1 mass%, and particularly preferably 0 mass%, relative to 100 mass% of the total mass of the solid components.

[0100] v) Organic carboxylic acids or phosphorus oxoacids or their derivatives Organic carboxylic acids or phosphorus oxo acids or derivatives thereof (hereinafter also referred to as "oxo acids, etc.") prevent sensitivity deterioration or improve resist pattern shape, delay stability, etc. Oxo acids, etc. may be used in combination with an acid diffusion controller or may be used alone. Suitable organic carboxylic acids include, for example, malonic acid, citric acid, malic acid, succinic acid, benzoic acid, salicylic acid, etc. Phosphorus oxo acids or derivatives thereof include phosphoric acid, phosphoric acid di-n-butyl ester, phosphoric acid diphenyl ester, etc., phosphoric acid or ester derivatives thereof, phosphonic acid, phosphonic acid dimethyl ester, phosphonic acid di-n-butyl ester, phenylphosphonic acid, phosphonic acid diphenyl ester, phosphonic acid dibenzyl ester, etc., phosphinic acid, phenylphosphinic acid, etc., phosphinic acid and ester derivatives thereof, and particularly preferred is phosphonic acid.

[0101] The oxoacids etc. can be used alone or in combination of two or more kinds. The amount of the oxoacids etc. is appropriately adjusted depending on the type of component (A) used, but is preferably 0 to 49 mass%, more preferably 0 to 5 mass%, further preferably 0 to 1 mass%, and particularly preferably 0 mass%, based on 100 mass% of the total mass of the solid components.

[0102] vi) Additives other than dissolution enhancers, dissolution regulators, sensitizers, oxo acids, etc. The resist composition may contain one or more additives other than the dissolution controller, sensitizer, surfactant, and oxo acid, as necessary. Examples of such additives include dyes, pigments, and adhesion aids. For example, the incorporation of a dye or pigment is preferable because it can visualize the latent image of the exposed area and mitigate the effect of halation during exposure. In addition, the incorporation of an adhesion aid is preferable because it can improve adhesion to the substrate. In addition, for example, an antihalation agent, a storage stabilizer, an antifoaming agent, a shape improver, and the like, specifically 4-hydroxy-4'-methylchalcone, can be added.

[0103] The total amount of component (F) in the resist composition is 0 to 99 mass%, preferably 0 to 49 mass%, more preferably 0 to 10 mass%, even more preferably 0 to 5 mass%, still more preferably 0 to 1 mass%, and particularly preferably 0 mass%, relative to 100 mass% of the total mass of solid components.

[0104] 5) Proportion of each ingredient The amount of component (A) in the resist composition is not limited, but is preferably 50 to 99.4 mass%, more preferably 55 to 90 mass%, even more preferably 60 to 80 mass%, and particularly preferably 60 to 70 mass%, of the total mass of the solid components being 100 mass% (the sum of components (A) and (C) to (F); the same applies below). When component (A) is contained in this amount, the resolution tends to be further improved and the line edge roughness (LER) tends to be further reduced.

[0105] The ratio of the components in the resist composition, i.e., component (A) / acid generator (component (C)) / acid crosslinker (component (G)) / acid diffusion controller (component (E)) / optional component (component (F)), is preferably the following, based on 100% by mass of the total mass of the solid components in the resist composition. By using these amounts, the sensitivity, resolution, developability, and other performance properties of the resist film tend to be further improved. 50~99.4 mass% / 0.001~49 mass% / 0.5~49 mass% / 0.001~49 mass% / 0~49 mass%, 55~90 mass% / 1~40 mass% / 0.5~40 mass% / 0.01~10 mass% / 0~5 mass%, 60~80% by mass / 3~30% by mass / 1~30% by mass / 0.01~5% by mass / 0~1% by mass, or 60~70 mass% / 10~25 mass% / 2~20 mass% / 0.01~3 mass% / 0 mass%

[0106] Furthermore, the resist composition may contain other resins other than those described above, if necessary. Examples of such resins include, but are not limited to, novolac resins, polyvinylphenols, polyacrylic acid, polyvinyl alcohol, styrene-maleic anhydride resins, and polymers containing acrylic acid, vinyl alcohol, or vinylphenol as monomer units, or derivatives thereof. The content of the resin is not particularly limited and is appropriately adjusted depending on the type of component (A) used, but is preferably 30 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 5 parts by mass or less, and particularly preferably 0 parts by mass, relative to 100 parts by mass of component (A).

[0107] 6) Preparation method The resist composition can be prepared by any method, for example, by dissolving each component in a solvent to prepare a homogeneous solution, and then filtering the solution, if necessary, through a filter having a pore size of about 0.2 μm.

[0108] 7) Physical properties of resist composition and resist film The resist composition can form an amorphous film by spin coating. The resist composition can be used in general semiconductor manufacturing processes. Depending on the type of developer used, either a positive resist pattern or a negative resist pattern can be produced.

[0109] In the case of a positive resist pattern, the dissolution rate of the amorphous film formed by spin-coating the resist composition in a developer at 23°C is preferably 5 Å / sec or less, more preferably 0.05 to 5 Å / sec, and even more preferably 0.0005 to 5 Å / sec. If the dissolution rate is 5 Å / sec or less, the film is insoluble in the developer, and it is easy to make it into a resist. If the dissolution rate is 0.0005 Å / sec or more, the resolution tends to improve. This is presumably because the contrast at the interface between the exposed part that dissolves in the developer and the unexposed part that does not dissolve in the developer increases due to the change in solubility of component (A) before and after exposure. In addition, the effect of reducing LER and defects is easily obtained.

[0110] In the case of a negative resist pattern, the dissolution rate of the amorphous film formed by spin-coating the resist composition in a developer at 23°C is preferably 10 Å / sec or more. If the dissolution rate is 10 Å / sec or more, the film is easily soluble in the developer, making it more suitable as a resist. In addition, if the dissolution rate is 10 Å / sec or more, the resolution also tends to improve. This is presumably because the micro surface portion of component (A) dissolves, reducing LER. Furthermore, the effect of reducing defects is more easily obtained.

[0111] The dissolution rate can be determined by immersing an amorphous film in a developer at 23° C. for a predetermined time, and measuring the film thickness before and after the immersion by a known method such as visual observation or cross-sectional observation using an ellipsometer or scanning electron microscope.

[0112] In the case of a positive resist pattern, the dissolution rate in a developer at 23°C of the portion of the amorphous film formed by spin-coating the resist composition of the present invention, which is exposed to radiation such as KrF excimer laser, extreme ultraviolet light, electron beam or X-ray (hereinafter also referred to as the "dissolution rate of the exposed portion"), is preferably 10 Å / sec or more. When the dissolution rate is 10 Å / sec or more, the film is easily soluble in a developer and is more suitable as a resist. In addition, when the dissolution rate is 10 Å / sec or more, the resolution tends to improve. This is presumably because the micro surface portion of component (A) dissolves, reducing LER. In addition, the effect of reducing defects is easily obtained.

[0113] In the case of a negative resist pattern, the dissolution rate of the exposed portion of the amorphous film formed by spin-coating the resist composition of the present invention is preferably 5 Å / sec or less, more preferably 0.05 to 5 Å / sec, and even more preferably 0.0005 to 5 Å / sec. If the dissolution rate is 5 Å / sec or less, the film is insoluble in a developer, and it is easy to make a resist. If the dissolution rate is 0.0005 Å / sec or more, the resolution tends to improve. This is presumably because the contrast of the interface between the unexposed portion that dissolves in the developer and the exposed portion that does not dissolve in the developer increases due to the change in solubility of component (A) before and after exposure. In addition, the effect of reducing LER and defects is easily obtained.

[0114] 8) Permanent resist film The resist film formed from the resist composition is suitable as a permanent film that remains in the final product. Specific examples of permanent films include, in the semiconductor device field, solder resist, packaging material, underfill material, package adhesive layer of circuit elements, and adhesive layer between integrated circuit elements and circuit boards, and in the thin display field, thin film transistor protective film, liquid crystal color filter protective film, black matrix, spacer, etc. The resist permanent film has the excellent advantage of being excellent in heat resistance and moisture resistance, and is less susceptible to contamination by sublimation components. The resist permanent film is a material that combines high sensitivity, high heat resistance, and moisture absorption reliability, which is important for display materials and reduces image quality deterioration due to contamination.

[0115] [Radiation sensitive composition] The radiation-sensitive composition of the present invention contains component (A), diazonaphthoquinone photoactive compound (B), and a solvent, and the amount of the solvent in the composition is 20 to 99% by mass, and the amount of components other than the solvent (solid content) is 1 to 80% by mass. The radiation-sensitive composition is useful as a base material for a positive resist that becomes a compound that is easily soluble in a developer when irradiated with g-rays, h-rays, i-rays, KrF excimer laser, ArF excimer laser, extreme ultraviolet rays, electron beams, or X-rays. Although the properties of component (A) do not change significantly due to g-rays, h-rays, i-rays, KrF excimer laser, ArF excimer laser, extreme ultraviolet rays, electron beams, or X-rays, the diazonaphthoquinone photoactive compound (component (B)), which is poorly soluble in a developer, is changed into a compound that is easily soluble, and a resist pattern can be formed by a development step. Since component (A) has a relatively low molecular weight, the roughness of the obtained resist pattern is very small.

[0116] The Tg of component (A) used in the radiation-sensitive composition is preferably 70° C. or higher, more preferably 80° C. or higher, even more preferably 100° C. or higher, and particularly preferably 150° C. or higher. There are no limitations on the upper limit of the Tg of component (A), but it is, for example, 400° C. or lower. When the Tg of component (A) is within this range, the composition has heat resistance capable of maintaining the pattern shape in the semiconductor lithography process, and performance such as high resolution is improved.

[0117] The crystallization heat of the component (A) used in the radiation-sensitive composition is preferably less than 20 J / g. In addition, (crystallization temperature)-(Tg) is preferably 70° C. or more, more preferably 80° C. or more, even more preferably 100° C. or more, and particularly preferably 130° C. or more. When the crystallization heat is less than 20 J / g or (crystallization temperature)-(Tg) is within the above range, an amorphous film is easily formed by spin-coating the radiation-sensitive composition, and the film-forming properties required for a resist can be maintained for a long period of time, which tends to improve the resolution.

[0118] The crystallization heat, crystallization temperature, and Tg can be determined by differential scanning calorimetry using a Shimadzu DSC / TA-50WS. Approximately 10 mg of the sample is placed in an aluminum non-sealed container and heated to above the melting point at a rate of 20°C / min in a nitrogen gas flow (50 mL / min). After quenching, the sample is heated again to above the melting point at a rate of 20°C / min in a nitrogen gas flow (30 mL / min). After further quenching, the sample is heated again to 400°C at a rate of 20°C / min in a nitrogen gas flow (30 mL / min). The temperature of the midpoint of the step of the stepped baseline (where the specific heat is halved) is the glass transition temperature (Tg), and the temperature of the exothermic peak that appears afterwards is the crystallization temperature. The amount of heat generated is calculated from the area of ​​the region surrounded by the exothermic peak and the baseline, and is taken as the amount of heat generated by crystallization.

[0119] The component (A) used in the radiation-sensitive composition preferably has low sublimation at normal pressure, 100°C or less, preferably 120°C or less, more preferably 130°C or less, even more preferably 140°C or less, and particularly preferably 150°C or less. Low sublimation means that the weight loss when held at a specific temperature for 10 minutes in thermogravimetric analysis is 10% or less, preferably 5% or less, more preferably 3% or less, even more preferably 1% or less, and particularly preferably 0.1% or less. Low sublimation can prevent contamination of the exposure device due to outgassing during exposure. In addition, there is a tendency to obtain a good pattern shape with low roughness.

[0120] 1) Diazonaphthoquinone photoactive compound (ingredient (B)) The diazonaphthoquinone photoactive compound (B) used in the radiation-sensitive composition is a diazonaphthoquinone substance including polymeric and non-polymeric diazonaphthoquinone photoactive compounds. In the present invention, there is no limitation so long as it is a compound generally used as a photosensitive component (photosensitizer) in a positive resist composition, and one or more kinds may be arbitrarily selected and used.

[0121] As such a photosensitizer, a compound obtained by reacting naphthoquinone diazide sulfonic acid chloride or benzoquinone diazide sulfonic acid chloride with a low molecular weight compound or a high molecular weight compound having a functional group capable of condensation reaction with the same is preferred. Here, the functional group capable of condensation with the acid chloride is not limited, but for example, a hydroxyl group, an amino group, etc. are mentioned, and in particular, a hydroxyl group is preferred. As a compound containing a hydroxyl group capable of condensation with the acid chloride, it is not limited, but for example, a hydroxyl group such as hydroquinone, resorcin, 2,4-dihydroxybenzophenone, 2,3,4-trihydroxybenzophenone, 2,4,6-trihydroxybenzophenone, 2,4,4'-trihydroxybenzophenone, 2,3,4,4'-tetrahydroxybenzophenone, 2,2',4,4'-tetrahydroxybenzophenone, and 2,2',3,4,6'-pentahydroxybenzophenone, etc. Examples of the hydroxyphenylalkanes include benzophenones, bis(2,4-dihydroxyphenyl)methane, bis(2,3,4-trihydroxyphenyl)methane, bis(2,4-dihydroxyphenyl)propane, and other hydroxytriphenylmethanes, such as 4,4',3",4"-tetrahydroxy-3,5,3',5'-tetramethyltriphenylmethane and 4,4',2",3",4"-pentahydroxy-3,5,3',5'-tetramethyltriphenylmethane.

[0122] Examples of naphthoquinone diazide sulfonic acid chlorides include 1,2-naphthoquinone diazide-5-sulfonyl chloride and 1,2-naphthoquinone diazide-4-sulfonyl chloride.

[0123] 2) Solvent The solvent used in the radiation-sensitive composition is selected from propylene glycol monomethyl ether acetate (PGMEA), propylene glycol monomethyl ether (PGME), cyclohexanone (CHN), cyclopentanone (CPN), 2-heptanone, anisole, butyl acetate, ethyl propionate, or ethyl lactate. Component (A) is dissolved in the solvent at 23° C., preferably at 1% by mass or more, more preferably at 5% by mass or more, and even more preferably at 10% by mass or more. The solvent is preferably selected from PGMEA, PGME, and CHN, and component (A) is dissolved in the solvent at 23° C., preferably at 20% by mass or more, and particularly preferably at 20% by mass or more in PGMEA at 23° C. When component (A) has this solubility, the possibility of using the radiation-sensitive composition in the semiconductor manufacturing process in practical production is increased. The amount of the solvent in the radiation-sensitive composition is 20 to 99 mass%, preferably 50 to 99 mass%, more preferably 60 to 98 mass%, and particularly preferably 90 to 98 mass%. The amount of components other than the solvent (solid components) in the radiation-sensitive composition is 1 to 80 mass%, preferably 1 to 50 mass%, more preferably 2 to 40 mass%, and particularly preferably 2 to 10 mass%.

[0124] 3) Preparation The method for preparing the radiation-sensitive composition is not limited; however, it is preferable to prepare the radiation-sensitive composition by, for example, dissolving each component in a solvent to prepare a homogeneous solution, and then, if necessary, filtering the solution through a filter having a pore size of about 0.2 μm.

[0125] 4) Characteristics of radiation-sensitive composition The radiation-sensitive composition can be used to form an amorphous film by spin coating. It can also be used in general semiconductor manufacturing processes. Depending on the type of developer used, it can produce either a positive resist pattern or a negative resist pattern.

[0126] In the case of a positive resist pattern, the dissolution rate of the amorphous film formed by spin-coating the radiation-sensitive composition in a developer at 23°C is preferably 5 Å / sec or less, more preferably 0.05 to 5 Å / sec, and even more preferably 0.0005 to 5 Å / sec. If the dissolution rate is 5 Å / sec or less, the film is insoluble in the developer, and it is easy to make it into a resist. If the dissolution rate is 0.0005 Å / sec or more, the resolution tends to improve. This is presumably because the contrast at the interface between the exposed part that dissolves in the developer and the unexposed part that does not dissolve in the developer increases due to the change in solubility of the component (A) before and after exposure. In addition, the effect of reducing LER and defects is easily obtained.

[0127] In the case of a negative resist pattern, the dissolution rate of the amorphous film formed by spin-coating the radiation-sensitive composition in a developer at 23°C is preferably 10 Å / sec or more. When the dissolution rate is 10 Å / sec or more, the film is easily soluble in the developer and is more suitable as a resist. In addition, when the film has a dissolution rate of 10 Å / sec or more, the resolution tends to improve. This is presumably because the micro surface portion of component (A) dissolves, reducing LER. In addition, the effect of reducing defects is easily obtained.

[0128] The dissolution rate can be determined by immersing an amorphous film in a developer at 23° C. for a predetermined time, and measuring the film thickness before and after the immersion by a known method such as visual observation, an ellipsometer, or a QCM method.

[0129] In the case of a positive resist pattern, the dissolution rate in a developer at 23°C of a portion of an amorphous film formed by spin-coating a radiation-sensitive composition and irradiated with radiation such as KrF excimer laser, extreme ultraviolet ray, electron beam or X-ray, or a portion exposed after heating at 20 to 500°C (hereinafter also referred to as "dissolution rate of exposed portion") is preferably 10 Å / sec or more, more preferably 10 to 10,000 Å / sec, and even more preferably 100 to 1,000 Å / sec. When the dissolution rate is 10 Å / sec or more, the resist is easily soluble in a developer and is more suitable as a resist. In addition, when the dissolution rate is 10,000 Å / sec or less, the resolution tends to improve. This is presumably because the micro surface portion of the component (A) dissolves, reducing LER. In addition, the effect of reducing defects is easily obtained.

[0130] In the case of a negative resist pattern, the dissolution rate of the exposed portion is preferably 5 Å / sec or less, more preferably 0.05 to 5 Å / sec, and even more preferably 0.0005 to 5 Å / sec. If the dissolution rate is 5 Å / sec or less, the resist is insoluble in the developer and can be easily made into a resist. If the dissolution rate is 0.0005 Å / sec or more, the resolution tends to improve. This is presumably because the contrast at the interface between the unexposed portion that dissolves in the developer and the exposed portion that does not dissolve in the developer increases due to the change in solubility of component (A) before and after exposure. In addition, the effect of reducing LER and defects is easily obtained.

[0131] 5) Other components (component (D)) The radiation-sensitive composition may contain, as necessary, a component (D) other than the components (A), (B), and the solvent. Examples of the component (D) include the above-mentioned acid generator, acid crosslinker, acid diffusion controller, dissolution promoter, dissolution controller, sensitizer, surfactant, organic carboxylic acid, phosphorus oxoacid or derivatives thereof, or combinations of these.

[0132] 6) Proportion of each component in the radiation-sensitive composition In the radiation-sensitive composition, the amount of component (A) is preferably 1 to 99 mass%, more preferably 5 to 95 mass%, further preferably 10 to 90 mass%, and particularly preferably 25 to 75 mass%, of the total mass of solid components (100 mass% (total of solid components such as components (A), (B), and (D)). When the amount of component (A) is within this range, a pattern with high sensitivity and small roughness tends to be obtained.

[0133] The amount of component (B) in the radiation-sensitive composition is preferably 1 to 99 mass%, more preferably 5 to 95 mass%, still more preferably 10 to 90 mass%, and particularly preferably 25 to 75 mass%, based on 100 mass% of the total mass of the solid components. When the amount of component (B) is within this range, a pattern with high sensitivity and small roughness tends to be obtained.

[0134] The content ratio ((A) / (B) / (D)) of component (A), diazonaphthoquinone photoactive compound (component (B)), and optional component (D) in the solid content of the radiation-sensitive composition is preferably as follows: 1~99% by mass / 99~1% by mass / 0~98% by mass, 1~99% by mass / 99~1% by mass / 0~49% by mass, 5~95% by mass / 95~5% by mass / 0~49% by mass, 10~90% by mass / 90~10% by mass / 0~10% by mass, 20~80% by mass / 80~20% by mass / 0~5% by mass, or 25~75% by mass / 75~25% by mass / 0% by mass.

[0135] The radiation-sensitive composition may contain a resin other than those described above. Examples of such resins include novolac resins, polyvinylphenols, polyacrylic acid, polyvinyl alcohol, styrene-maleic anhydride resins, and polymers containing acrylic acid, vinyl alcohol, or vinylphenol as monomer units, or derivatives thereof. The amount of these resins is appropriately adjusted depending on the type of component (A) used, but is preferably 30 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 5 parts by mass or less, and particularly preferably 0 parts by mass, relative to 100 parts by mass of component (A).

[0136] [Underlayer film forming composition for lithography] Among the compositions containing the prepolymer of the present invention, those suitable for forming an underlayer film for lithography are referred to as an underlayer film-forming composition for lithography. The underlayer film-forming composition for lithography contains component (A) and components such as a solvent, a crosslinking agent, or an acid generator. 1) Solvent The solvent is as described in the resist composition. The amount of the solvent in the underlayer film-forming composition for lithography is not limited, but from the viewpoints of solubility and film formation, it is preferably 100 to 10,000 parts by mass, more preferably 200 to 5,000 parts by mass, and even more preferably 200 to 1,000 parts by mass relative to 100 parts by mass of the component (A).

[0137] 2) Crosslinking agent The underlayer film-forming composition for lithography may contain a crosslinking agent from the viewpoint of suppressing intermixing. The crosslinking agent is not limited, but examples thereof include epoxy compounds, amino compounds, benzoxazine compounds, acrylate compounds, melamine compounds, guanamine compounds, glycoluril compounds, urea compounds, isocyanate compounds, azide compounds, phenol compounds, and cyanate compounds. Specific examples of these crosslinking agents include those described in International Publication No. 2018 / 016614 and International Publication No. 2013 / 024779. These crosslinking agents are used alone or in combination of two or more. Among these, melamine compounds, benzoxazine compounds, glycoluril compounds, and epoxy compounds are preferred, and melamine compounds and benzoxazine compounds are more preferred from the viewpoint of improving etching resistance.

[0138] The content of the crosslinking agent is not limited, but is preferably 0.1 to 100 parts by mass, more preferably 5 to 50 parts by mass, and even more preferably 10 to 40 parts by mass, relative to 100 parts by mass of component (A). By having the content of the crosslinking agent within the above range, the occurrence of the mixing phenomenon with the resist layer tends to be suppressed, and the antireflection effect tends to be enhanced, and the film formability after crosslinking tends to be improved.

[0139] 3) Crosslinking accelerator The underlayer film-forming composition for lithography may contain a crosslinking accelerator to accelerate the crosslinking reaction (curing reaction) as necessary. Examples of the crosslinking accelerator include radical polymerization initiators. Examples of the radical polymerization initiator may be photopolymerization initiators that initiate radical polymerization by light, or thermal polymerization initiators that initiate radical polymerization by heat. Examples of the radical polymerization initiator include at least one selected from the group consisting of ketone-based photopolymerization initiators, organic peroxide-based polymerization initiators, and azo-based polymerization initiators.

[0140] Such radical polymerization initiators are not particularly limited, and examples thereof include those described in WO 2018 / 016614.

[0141] 4) Acid generator The underlayer film-forming composition for lithography may contain an acid generator. The acid generator is as described in the resist composition. The amount of the acid generator is not limited, but is preferably 0.1 to 50 parts by mass, and more preferably 0.5 to 40 parts by mass, relative to 100 parts by mass of component (A). When the content of the acid generator is within the above range, the crosslinking reaction tends to be enhanced, and the occurrence of the mixing phenomenon with the resist layer tends to be suppressed.

[0142] 5) Basic compounds The underlayer film-forming composition for lithography may contain a basic compound from the viewpoint of improving storage stability. The basic compound plays a role of preventing a small amount of acid generated from the acid generator from proceeding with a crosslinking reaction, that is, plays a role of a quencher for the acid. Such a basic compound is not limited, but may be, for example, one described in International Publication No. 2013 / 024779.

[0143] The amount of the basic compound is not limited, but is preferably 0.001 to 2 parts by mass, more preferably 0.01 to 1 part by mass, relative to 100 parts by mass of the film-forming material for lithography. By having the content of the basic compound within the above range, storage stability tends to be improved without excessively impairing the crosslinking reaction.

[0144] 6) Other additives The underlayer film-forming composition for lithography may contain other resins or compounds for the purpose of imparting curability by heat or light or controlling absorbance. Examples of such resins or compounds include, but are not limited to, naphthol resins, xylene resins, naphthol-modified resins, and phenol-modified resins of naphthalene resins; polyhydroxystyrene, dicyclopentadiene resins, (meth)acrylates, dimethacrylates, trimethacrylates, tetramethacrylates, vinylnaphthalene, polyacenaphthylene, and other naphthalene rings, phenanthrenequinone, fluorene, and other biphenyl rings, thiophene, indene, and other heteroatom-containing heterocycles and aromatic ring-free resins; rosin-based resins, cyclodextrins, adamantane (poly)ols, tricyclodecane (poly)ols, and derivatives thereof, and other resins or compounds containing alicyclic structures. The underlayer film-forming composition for lithography may contain known additives. Examples of known additives include, but are not limited to, heat or light curing catalysts, polymerization inhibitors, flame retardants, fillers, coupling agents, thermosetting resins, photocurable resins, dyes, pigments, thickeners, lubricants, defoamers, leveling agents, ultraviolet absorbers, surfactants, colorants, and nonionic surfactants.

[0145] [Optical component forming composition and its cured product] Among the compositions containing the prepolymer of the present invention, those suitable for forming optical parts are called optical part forming compositions. Optical parts formed from the composition are expected to have a high refractive index and high transparency, and further, are expected to have storage stability, structure forming ability (film forming ability), and heat resistance. In addition, the cured product obtained by curing the composition can be a three-dimensional crosslinked product, and coloring is suppressed by a wide range of heat treatment from low temperature to high temperature, and a high refractive index and high transparency can be expected. The refractive index and degree of transparency of the optical part are not limited, but it is preferable that the refractive index is 1.65 to 2.00% and the extinction coefficient (transparency) is 0.001 to 0.03 at a wavelength of 633 nm. The refractive index and extinction coefficient are measured using a vacuum ultraviolet region multiple incidence angle spectroscopic ellipsometer.

[0146] 1) Solvent The optical part forming composition may contain a solvent. The solvent may be the same as the solvent used in the lithography material composition of the present embodiment described above.

[0147] The relationship between the amount of solid component and the amount of solvent in the optical component-forming composition is not limited, but the solid component is preferably 1 to 80 mass % and the solvent is 20 to 99 mass %, more preferably 1 to 50 mass % and the solvent is 50 to 99 mass %, further preferably 2 to 40 mass % and the solvent is 60 to 98 mass %, and particularly preferably 2 to 10 mass % and the solvent is 90 to 98 mass %. The optical component-forming composition may not contain a solvent.

[0148] 2) Amount of each ingredient The optical component-forming composition may contain, as another solid component, at least one selected from the group consisting of the acid generator (component (C)), the acid crosslinker (component (G)), the acid diffusion controller (component (E)) and other components (F).

[0149] The amount of component (A) in the optical component-forming composition, relative to the total mass of solid components (100 mass%), is preferably 50 to 99.4 mass%, more preferably 55 to 90 mass%, even more preferably 60 to 80 mass%, and particularly preferably 60 to 70 mass%.

[0150] When the optical component-forming composition contains an acid generator (component (C)), the amount thereof is preferably 0.001 to 49 mass%, more preferably 1 to 40 mass%, further preferably 3 to 30 mass%, and particularly preferably 10 to 25 mass%, based on 100 mass% of the total mass of the solid components. By using the acid generator within the above content range, a cured product with a higher refractive index can be obtained.

[0151] From the viewpoint of improving the strength of the cured product, the optical component-forming composition preferably contains one or more acid crosslinkers (component (G)). The content of the acid crosslinker is preferably 0.5 to 49 mass%, more preferably 0.5 to 40 mass%, further preferably 1 to 30 mass%, and particularly preferably 2 to 20 mass%, based on 100 mass% of the total mass of the solid components. When the content of the acid crosslinker is 0.5 mass% or more, the effect of suppressing the solubility of the optical component-forming composition in organic solvents can be improved, which is preferable, while when the content is 49 mass% or less, the decrease in heat resistance of the optical component-forming composition can be suppressed, which is preferable.

[0152] The optical component-forming composition may contain an acid diffusion controller (component (E)). The use of an acid diffusion controller improves the storage stability of the optical component-forming composition.

[0153] The content of the acid diffusion controller is preferably 0.001 to 49% by mass, more preferably 0.01 to 10% by mass, further preferably 0.01 to 5% by mass, and particularly preferably 0.01 to 3% by mass, based on 100% by mass. When the content of the acid diffusion controller is within the above range, deterioration of dimensional fidelity and the like can be further suppressed. In addition, by using such an acid diffusion controller, the storage stability of the optical component forming composition is improved, the resolution is improved, and the process stability is extremely excellent.

[0154] When the optical component-forming composition contains the optional component (F), the total amount thereof is preferably 0 to 49 mass % of the total mass of the solid components, more preferably 0 to 5 mass %, even more preferably 0 to 1 mass %, and particularly preferably 0 mass %.

[0155] In the composition for forming an optical part, the contents of component (A), component (C), component (E) and component (F) are preferably as follows. 50~99.4 mass% / 0.001~49 mass% / 0.001~49 mass% / 0~49 mass%, 55~90 mass% / 1~40 mass% / 0.01~10 mass% / 0~5 mass% 60~80% by mass / 3~30% by mass / 0.01~5% by mass / 0~1% by mass, or 60~70% by mass / 10~25% by mass / 0.01~3% by mass / 0% by mass.

[0156] The method for preparing the optical part-forming composition is not limited, and examples include a method in which each component is dissolved in a solvent to form a homogeneous solution, and then, if necessary, filtered through a filter with a pore size of about 0.2 μm.

[0157] The optical component forming composition may contain a resin to the extent that the object of the present invention is not hindered. The resin is not particularly limited, and examples thereof include novolac resins, polyvinylphenols, polyacrylic acid, polyvinyl alcohol, styrene-maleic anhydride resins, and polymers containing acrylic acid, vinyl alcohol, or vinylphenol as monomer units, or derivatives thereof. The content of the resin is not particularly limited and is appropriately adjusted depending on the type of component (A) used, but is preferably 30 parts by mass or less, more preferably 10 parts by mass or less, even more preferably 5 parts by mass or less, and particularly preferably 0 parts by mass, per 100 parts by mass of component (A).

[0158] 3) Cured product The cured product is obtained by curing the optical component-forming composition and can be used as various resins. These cured products can be used for various purposes as highly versatile materials that impart various properties such as a high melting point, a high refractive index, and high transparency. The cured product can be obtained by applying a known method corresponding to each composition, such as irradiating the composition with light or heating it.

[0159] These cured products can be used as various synthetic resins such as epoxy resins, polycarbonate resins, and acrylic resins, and further, taking advantage of their functionality, can be used as optical parts such as lenses and optical sheets.

[0160] 3. Method for forming a film or resist pattern [Method of forming a resist pattern using a resist composition] The method for forming a resist pattern using the resist composition of the present invention comprises the steps of forming a resist film on a substrate using the composition, exposing at least a part of the formed resist film, and developing the exposed resist film to form a resist pattern. The resist pattern can also be formed as an upper layer resist in a multi-layer process. The method for forming a resist pattern can also be used as a method for forming a permanent resist film, which will be described later.

[0161] The method for forming the resist pattern is not limited, but may be, for example, the following method. First, a resist film is formed by applying a resist composition onto a conventionally known substrate by a coating means such as spin coating, casting coating, or roll coating. The conventionally known substrate is not particularly limited, and may be, for example, a substrate for electronic components, or a substrate on which a predetermined wiring pattern is formed. More specifically, but not particularly limited, may be a silicon wafer, a substrate made of metal such as copper, chromium, iron, or aluminum, or a glass substrate. The material of the wiring pattern is not particularly limited, and may be, for example, copper, aluminum, nickel, or gold. If necessary, an inorganic or organic film may be provided on the substrate. The inorganic film is not particularly limited, but may be, for example, an inorganic anti-reflective film (inorganic BARC). The organic film is not particularly limited, but may be, for example, an organic anti-reflective film (organic BARC). Surface treatment may be performed using hexamethylenedisilazane or the like.

[0162] Next, the coated substrate is heated as necessary. The heating conditions vary depending on the composition of the resist composition, etc., but are preferably 20 to 250°C, more preferably 20 to 150°C. Heating is preferable because it may improve the adhesion of the resist to the substrate. Next, the resist film is exposed to a desired pattern by any radiation selected from the group consisting of visible light, ultraviolet light, excimer laser, electron beam, extreme ultraviolet light (EUV), X-rays, and ion beams. The exposure conditions, etc. are appropriately selected depending on the composition of the resist composition, etc. In order to stably form a high-precision fine pattern in exposure, it is preferable to heat after radiation irradiation.

[0163] Next, the exposed resist film is developed with a developer to form a predetermined resist pattern. As the developer, it is preferable to select a solvent having a solubility parameter (SP value) close to that of the component (A) used, and polar solvents such as ketone-based solvents, ester-based solvents, alcohol-based solvents, amide-based solvents, and ether-based solvents, hydrocarbon-based solvents, or alkaline aqueous solutions can be used. Specific examples of these developers include those described in International Publication No. 2018 / 016614.

[0164] The above solvents may be mixed in plural, or may be mixed with other solvents or water within the range of performance. However, in order to fully achieve the effects of the present invention, the water content of the developer as a whole is preferably less than 70% by mass, more preferably less than 50% by mass, even more preferably less than 30% by mass, even more preferably less than 10% by mass, and particularly preferably substantially no water. That is, the content of the organic solvent in the developer is preferably 30% by mass or more and 100% by mass or less, more preferably 50% by mass or more and 100% by mass or less, even more preferably 70% by mass or more and 100% by mass or less, even more preferably 90% by mass or more and 100% by mass or less, and particularly preferably 95% by mass or more and 100% by mass or less, based on the total amount of the developer.

[0165] As the developer, a developer containing at least one solvent selected from a ketone-based solvent, an ester-based solvent, an alcohol-based solvent, an amide-based solvent, and an ether-based solvent is particularly preferred because it improves resist performance such as the resolution and roughness of the resist pattern.

[0166] If necessary, a suitable amount of a surfactant may be added to the developer. The surfactant is not particularly limited, but for example, an ionic or non-ionic fluorine-based or silicon-based surfactant may be used. Examples of these fluorine- or silicon-based surfactants include those described in JP-A-62-36663, JP-A-61-226746, JP-A-61-226745, JP-A-62-170950, JP-A-63-34540, JP-A-7-230165, JP-A-8-62834, JP-A-9-54432, JP-A-9-5988, U.S. Pat. Nos. 5,405,720, 5,360,692, 5,529,881, 5,296,330, 5,436,098, 5,576,143, 5,294,511, and 5,824,451, and preferably nonionic surfactants. The non-ionic surfactant is not particularly limited, but it is more preferable to use a fluorine-based surfactant or a silicon-based surfactant.

[0167] The amount of the surfactant used is usually from 0.001 to 5% by mass, preferably from 0.005 to 2% by mass, and more preferably from 0.01 to 0.5% by mass, based on the total amount of the developer.

[0168] The developing method is not particularly limited, but may be, for example, a method of immersing a substrate in a tank filled with a developer for a certain period of time (dip method), a method of piling up the developer on the substrate surface by surface tension and leaving it still for a certain period of time (paddle method), a method of spraying the developer on the substrate surface (spray method), or a method of continuously dispensing the developer while scanning a developer dispensing nozzle at a constant speed on a substrate rotating at a constant speed (dynamic dispense method). The time for developing the pattern is not limited, but is preferably 10 seconds to 90 seconds. After the developing step, a step of stopping the development by replacing the solvent with another solvent may be performed.

[0169] After development, it is preferable to include a step of washing with a rinse solution containing an organic solvent. The rinse solution used in the rinse step after development is not particularly limited as long as it does not dissolve the resist pattern hardened by crosslinking, and a solution containing a general organic solvent or water can be used. As the rinse solution, it is preferable to use a rinse solution containing at least one organic solvent selected from a hydrocarbon solvent, a ketone solvent, an ester solvent, an alcohol solvent, an amide solvent, and an ether solvent. More preferably, after development, a step of washing is performed with a rinse solution containing at least one organic solvent selected from the group consisting of a ketone solvent, an ester solvent, an alcohol solvent, and an amide solvent. More preferably, after development, a step of washing is performed with a rinse solution containing an alcohol solvent or an ester solvent. Even more preferably, after development, a step of washing is performed with a rinse solution containing a monohydric alcohol. Particularly preferably, after development, a step of washing is performed with a rinse solution containing a monohydric alcohol having 5 or more carbon atoms. The time for rinsing the pattern is not limited, but is preferably 10 to 90 seconds.

[0170] Examples of the monohydric alcohol used in the rinse step after development include linear, branched, and cyclic monohydric alcohols, and are not particularly limited. For example, 1-butanol, 2-butanol, 3-methyl-1-butanol, tert-butyl alcohol, 1-pentanol, 2-pentanol, 1-hexanol, 4-methyl-2-pentanol, 1-heptanol, 1-octanol, 2-hexanol, cyclopentanol, 2-heptanol, 2-octanol, 3-hexanol, 3-heptanol, 3-octanol, and 4-octanol can be used. Particularly preferred monohydric alcohols having 5 or more carbon atoms include 1-hexanol, 2-hexanol, 4-methyl-2-pentanol, 1-pentanol, and 3-methyl-1-butanol. The above-mentioned components may be mixed in plural, or may be mixed with an organic solvent other than the above.

[0171] The water content in the rinse solution is preferably 10% by mass or less, more preferably 5% by mass or less, and particularly preferably 3% by mass or less. By making the water content 10% by mass or less, better development characteristics tend to be obtained. The rinse solution can also be used by adding an appropriate amount of a surfactant.

[0172] In the rinsing step, the developed wafer is washed with a rinse solution containing the organic solvent. The method of the washing is not particularly limited, but may be, for example, a method of continuously applying the rinse solution onto a substrate rotating at a constant speed (spin coating method), a method of immersing the substrate in a tank filled with the rinse solution for a certain period of time (dip method), or a method of spraying the rinse solution onto the substrate surface (spray method), and among these, it is preferable to perform the washing by the spin coating method, rotate the substrate at a rotation speed of 2000 rpm to 4000 rpm after washing, and remove the rinse solution from the substrate.

[0173] After forming the resist pattern, the resist pattern is etched to obtain a patterned wiring board. The etching method can be a known method such as dry etching using plasma gas or wet etching using an alkaline solution, a cupric chloride solution, a ferric chloride solution, or the like.

[0174] After the resist pattern is formed, plating can be performed, for example, by copper plating, solder plating, nickel plating, gold plating, etc.

[0175] The remaining resist pattern after etching can be peeled off with an organic solvent. The organic solvent is not particularly limited, but examples thereof include PGMEA (propylene glycol monomethyl ether acetate), PGME (propylene glycol monomethyl ether), and EL (ethyl lactate). The peeling method is not limited, but examples thereof include a dipping method and a spray method. In addition, the wiring board on which the resist pattern is formed may be a multilayer wiring board and may have a small diameter through hole.

[0176] The wiring board can also be formed by a method in which a resist pattern is formed, a metal is evaporated in a vacuum, and then the resist pattern is dissolved in a solution, that is, by a lift-off method.

[0177] The resist pattern forming method may include an underlayer film forming step of forming an underlayer film on a substrate using an underlayer film forming composition for lithography. The forming method of this embodiment includes a photoresist layer forming step of forming at least one photoresist layer on the underlayer film formed in the underlayer film forming step, and a step of irradiating a predetermined area of ​​the photoresist layer formed in the photoresist layer forming step with radiation and developing it. The resist pattern forming method of this embodiment can be used to form various patterns, but is preferably a method for forming an insulating film pattern. The underlayer film forming step will be described later.

[0178] [Undercoat for lithography] The method for producing the underlayer film for lithography from the film-forming composition for lithography is not limited, and a known method can be used. For example, the film-forming composition for lithography is placed on a substrate by a known coating method such as spin coating or screen printing, a printing method, or the like, and then the organic solvent is removed by volatilization, or the like, to form the underlayer film. When forming the underlayer film, it is preferable to perform baking in order to suppress the occurrence of a mixing phenomenon with the resist upper layer film and to promote the crosslinking reaction. In this case, the baking temperature is not limited, but is preferably 80 to 450°C, more preferably 200 to 400°C. The baking time is also not limited, but is preferably within the range of 10 to 600 seconds. The thickness of the underlayer film can be appropriately selected depending on the required performance, and is not limited, but is preferably 30 to 20,000 nm, more preferably 50 to 15,000 nm.

[0179] After preparing the underlayer film, in the case of a two-layer process, it is preferable to prepare a silicon-containing resist layer or a monolayer resist made of hydrocarbon on the underlayer film, and in the case of a three-layer process, it is preferable to prepare a silicon-containing intermediate layer on the underlayer film, and further prepare a silicon-free monolayer resist layer on the silicon-containing intermediate layer.In this case, the photoresist material for forming this resist layer can be a known one.

[0180] As a silicon-containing resist material for a two-layer process, from the viewpoint of oxygen gas etching resistance, a positive photoresist material is preferably used which uses a silicon atom-containing polymer such as a polysilsesquioxane derivative or a vinylsilane derivative as a base polymer, and further contains an organic solvent, an acid generator, and if necessary, a basic compound, etc. Here, as the silicon atom-containing polymer, a known polymer used in this type of resist material can be used.

[0181] As the silicon-containing intermediate layer for the three-layer process, a polysilsesquioxane-based intermediate layer is preferably used. By giving the intermediate layer an effect as an anti-reflection film, reflection tends to be effectively suppressed. For example, in a 193 nm exposure process, if a material containing many aromatic groups and having high substrate etching resistance is used as the underlayer film, the k value tends to be high and the substrate reflection tends to be high, but by suppressing reflection with the intermediate layer, the substrate reflection can be reduced to 0.5% or less. As the intermediate layer having such an anti-reflection effect, it is not limited to the following, but for 193 nm exposure, a polysilsesquioxane that is crosslinked by acid or heat and has a light-absorbing group having a phenyl group or a silicon-silicon bond introduced therein is preferably used.

[0182] An intermediate layer formed by a chemical vapor deposition (CVD) method can also be used. As an intermediate layer produced by a CVD method and having a high effect as an anti-reflection film, for example, a SiON film is known, but is not limited to the following. In general, it is easier and more cost-effective to form an intermediate layer by a wet process such as a spin coating method or screen printing than by a CVD method. The upper layer resist in the three-layer process may be either a positive type or a negative type, and the same resist as a commonly used single layer resist can be used.

[0183] Furthermore, the underlayer film of the present invention can be used as an anti-reflective film for a normal single-layer resist or as an underlayer material for suppressing pattern collapse. Since the underlayer film has excellent etching resistance for underlayer processing, it can also be expected to function as a hard mask for underlayer processing.

[0184] When forming a resist layer using the photoresist material, a wet process such as spin coating or screen printing is preferably used, as in the case of forming the underlayer film. After applying the resist material by spin coating or the like, pre-baking is usually performed, and this pre-baking is preferably performed at 80 to 180° C. for 10 to 300 seconds. Thereafter, exposure is performed according to a conventional method, followed by post-exposure baking (PEB) and development to obtain a resist pattern. The thickness of the resist film is not particularly limited, but generally, it is preferably 30 to 500 nm, more preferably 50 to 400 nm.

[0185] The exposure light is appropriately selected according to the photoresist material used. In general, high energy rays with a wavelength of 300 nm or less, specifically, excimer lasers with wavelengths of 248 nm, 193 nm, and 157 nm, soft X-rays with wavelengths of 3 to 20 nm, electron beams, X-rays, etc. can be mentioned. The resist pattern formed by the above-mentioned method is one in which pattern collapse is suppressed by the underlayer film. Therefore, by using the underlayer film, a finer pattern can be obtained, and the exposure dose required to obtain the resist pattern can be reduced.

[0186] Next, etching is performed using the obtained resist pattern as a mask. Gas etching is preferably used for etching the lower layer film in the two-layer process. Etching using oxygen gas is suitable for gas etching. In addition to oxygen gas, it is possible to add inert gases such as He and Ar, or CO, CO2, NH3, SO2, N2, NO2, and H2 gases. Gas etching can also be performed using only CO, CO2, NH3, SO2, N2, NO2, and H2 gases without using oxygen gas. In particular, the latter gas is preferably used for sidewall protection to prevent undercutting of the pattern sidewall.

[0187] On the other hand, gas etching is also preferably used for etching the middle layer in the three-layer process. The gas etching can be the same as that described in the two-layer process. In particular, the processing of the middle layer in the three-layer process is preferably performed using a fluorocarbon-based gas and a resist pattern as a mask. Then, as described above, the processing of the lower layer film can be performed by, for example, performing oxygen gas etching using the middle layer pattern as a mask.

[0188] Here, when forming an inorganic hard mask intermediate layer film as the intermediate layer, a silicon oxide film, a silicon nitride film, or a silicon oxynitride film (SiON film) is formed by a CVD method, an ALD method, or the like. The method for forming the nitride film is not limited to the following, but for example, the methods described in JP-A-2002-334869 and WO2004 / 066377 can be used. A photoresist film can be formed directly on such an intermediate layer film, but an organic anti-reflective coating (BARC) may be formed on the intermediate layer film by spin coating, and a photoresist film may be formed on the organic anti-reflective coating (BARC).

[0189] As the intermediate layer, a polysilsesquioxane-based intermediate layer is also preferably used. By giving the resist intermediate layer film an effect as an anti-reflection film, reflection tends to be effectively suppressed. The specific material of the polysilsesquioxane-based intermediate layer is not limited to the following, but for example, those described in JP-A-2007-226170 and JP-A-2007-226204 can be used. In addition, the next etching of the substrate can also be performed by a conventional method. For example, if the substrate is SiO2 or SiN, etching can be performed mainly with fluorocarbon-based gas, and if it is p-Si, Al, or W, etching can be performed mainly with chlorine-based or bromine-based gas. When etching the substrate with fluorocarbon-based gas, the silicon-containing resist of the two-layer resist process and the silicon-containing intermediate layer of the three-layer process are stripped at the same time as the substrate is processed. On the other hand, when the substrate is etched with chlorine-based or bromine-based gas, the silicon-containing resist layer or the silicon-containing intermediate layer is stripped separately, and generally, dry etching stripping with fluorocarbon-based gas is performed after the substrate is processed.

[0190] The underlayer film of the present invention is characterized by excellent resistance to etching of the substrate. The substrate can be appropriately selected from known ones and includes, but is not limited to, Si, α-Si, p-Si, SiO2, SiN, SiON, W, TiN, Al, etc. The substrate may also be a laminate having a film to be processed (substrate to be processed) on a base material (support). Examples of such a film to be processed include various low-k films and their stopper films, such as Si, SiO2, SiON, SiN, p-Si, α-Si, W, W-Si, Al, Cu, Al-Si, etc., and films made of a material different from that of the base material (support) are usually used. The thickness of the substrate or film to be processed is not limited, but is usually preferably about 50 to 1,000,000 nm, more preferably 75 to 50,000 nm.

[0191] [Pattern formation method] The pattern forming method includes the following: an underlayer film forming step of forming an underlayer film on a substrate using the underlayer film forming composition for lithography of the present invention; an intermediate layer film forming step of forming an intermediate layer film on the underlayer film formed by the underlayer film forming step using a resist intermediate layer film material containing silicon atoms; a photoresist layer forming step of forming at least one photoresist layer on the intermediate layer film formed by the intermediate layer film forming step; a resist pattern forming step of irradiating a predetermined area of ​​the photoresist layer formed by the photoresist layer forming step with radiation and developing it to form a resist pattern; an intermediate layer film pattern forming step of etching the intermediate layer film using the resist pattern formed by the resist pattern forming step as a mask to form an intermediate layer film pattern; an underlayer film pattern forming step of etching the underlayer film using the intermediate layer film pattern formed by the intermediate layer film pattern forming step as a mask to form an underlayer film pattern; and a substrate pattern forming step of etching the substrate using the underlayer film pattern formed by the underlayer film pattern forming step as a mask to form a pattern on the substrate. A process of forming a conductor layer can be further added to these steps to form a circuit forming method.

[0192] [Permanent resist film] The resist permanent film of this embodiment contains the above-mentioned composition. The resist permanent film formed by applying the composition is suitable as a permanent film that remains in the final product after forming a resist pattern as necessary. Specific examples of permanent films include solder resist, packaging material, underfill material, package adhesive layer of circuit elements, etc., and adhesive layer between integrated circuit elements and circuit boards in semiconductor device-related applications, and thin film transistor protective film, liquid crystal color filter protective film, black matrix, spacer, etc. in thin display-related applications. In particular, the resist permanent film containing the composition has the excellent advantages of being excellent in heat resistance and moisture resistance, and being less susceptible to contamination by sublimation components. In particular, in display materials, the material is a material that combines high sensitivity, high heat resistance, and moisture absorption reliability with little image quality deterioration due to important contamination.

[0193] When the composition for forming an underlayer film for lithography of the present embodiment is used for a permanent resist film application, in addition to a curing agent, various additives such as other resins, surfactants, dyes, fillers, crosslinking agents, and dissolution promoters can be added as necessary, and the composition can be dissolved in an organic solvent to form a composition for a permanent resist film.

[0194] The composition can be prepared by blending the above-mentioned components and mixing them using a stirrer, etc. When the composition contains a filler or a pigment, it can be prepared by dispersing or mixing them using a dispersing device such as a dissolver, homogenizer, or three-roll mill.

[0195] 4. Purification method The method for purifying a prepolymer of the present invention includes an extraction step in which a solution containing the prepolymer and an organic solvent that is not miscible with water is contacted with an acidic aqueous solution. Specifically, the prepolymer is dissolved in an organic solvent that is not miscible with water, and the solution is contacted with an acidic aqueous solution to perform an extraction treatment, whereby metals contained in the prepolymer are transferred to the aqueous phase, and the organic phase and the aqueous phase are separated and purified. This method can significantly reduce the content of various metals in the prepolymer of the present invention.

[0196] The organic solvent that is not miscible with water refers to an organic solvent that has a solubility in water of less than 50% by mass at any temperature between 20 and 90°C. From the viewpoint of productivity, the solubility is preferably less than 25% by mass. The organic solvent that is not miscible with water is not limited, but is preferably an organic solvent that can be safely applied to the semiconductor manufacturing process. The amount of the organic solvent used is usually about 1 to 100 times by mass relative to the prepolymer of the present invention.

[0197] Specific examples of the solvent used in the purification method of the present invention include those described in International Publication WO2015 / 080240. These solvents are used alone or in combination of two or more. Among these, toluene, 2-heptanone, cyclohexanone, cyclopentanone, methyl isobutyl ketone, propylene glycol monomethyl ether acetate, ethyl acetate, etc. are preferred, and cyclohexanone and propylene glycol monomethyl ether acetate are particularly preferred.

[0198] The acidic aqueous solution is appropriately selected from among aqueous solutions in which a generally known organic or inorganic compound is dissolved in water. For example, those described in International Publication WO2015 / 080240 can be mentioned. These acidic aqueous solutions are used alone or in combination of two or more. Among these, aqueous solutions of inorganic acids such as sulfuric acid and nitric acid, or organic acids such as acetic acid, oxalic acid, tartaric acid, and citric acid are preferred, aqueous solutions of sulfuric acid, oxalic acid, tartaric acid, and citric acid are preferred, and aqueous solutions of oxalic acid are particularly preferred. Polycarboxylic acids such as oxalic acid, tartaric acid, and citric acid are coordinated to metal ions and exhibit a chelating effect, so that it is considered that a higher removal effect is achieved. In this case, water with a low metal content, such as ion-exchanged water, is preferably used in accordance with the object of the present invention.

[0199] The pH of the acidic aqueous solution is not limited, but an aqueous solution with an excessively high acidity is not preferred because it may adversely affect the prepolymer of the present invention. The pH range is usually about 0 to 5, and more preferably about 0 to 3.

[0200] The amount of the acidic aqueous solution used is not limited, but if the amount is too small, extraction must be performed many times to remove the metal, and conversely, if the amount is too large, the total amount of liquid increases and workability may decrease. The amount of the aqueous solution used is usually 10 to 200% by mass, preferably 20 to 100% by mass, based on the solution containing the prepolymer of the present invention and the organic solvent.

[0201] The temperature during the extraction treatment is usually 20 to 90°C, and preferably in the range of 30 to 80°C. The extraction operation is carried out, for example, by thoroughly mixing the two by stirring or the like, and then allowing to stand. As a result, the metal content contained in the prepolymer of the present invention is transferred to the aqueous phase. In addition, this treatment reduces the acidity of the solution, making it possible to suppress deterioration of the prepolymer of the present invention.

[0202] The oil phase containing the prepolymer of the present invention is recovered from the mixture after the treatment by decantation or the like. The time for leaving the mixture standing is not limited, but if the time for leaving the mixture standing is too short, the oil phase containing the organic solvent and the aqueous phase will not be sufficiently separated, which is not preferable. The time for leaving the mixture standing is usually 1 minute or more, more preferably 10 minutes or more, and even more preferably 30 minutes or more. The extraction treatment may be performed once or multiple times.

[0203] The recovered oil phase is preferably subjected to a washing treatment with water, i.e., an extraction treatment using water. This treatment can be carried out as described above. The oil phase obtained after washing may contain water, but the water can be easily removed by vacuum distillation or the like. If necessary, an organic solvent can be added to the oil phase to adjust the concentration of the prepolymer of the present invention. The target prepolymer can be isolated by subjecting the oil phase to known treatments such as vacuum distillation and reprecipitation. EXAMPLES

[0204] The present embodiment will be described in more detail below with reference to examples and comparative examples, but the present embodiment is not limited thereto.

[0205] The prepolymer in this embodiment was analyzed and evaluated as follows. 1 H-NMR and 13 C-NMR measurements were performed using a Bruker Advance 600II spectrometer under the following conditions. Frequency: 400MHz Solvent: d6-DMSO Internal standard: TMS Measurement temperature: 23℃

[0206] <Polystyrene equivalent molecular weight> The weight average molecular weight (Mw) and number average molecular weight (Mn) in terms of polystyrene were determined by gel permeation chromatography (GPC) analysis, and the polydispersity (Mw / Mn) was also determined. Equipment: Shodex GPC-101 (Showa Denko Co., Ltd.) Column: Agilent Technologies PLgel 5μm Mixed-C column Eluent: DMAc 1mL / min Temperature: 40℃

[0207] <Measurement of thermal decomposition temperature> Using an EXSTAR6000TG / DTA device manufactured by SII NanoTechnology, approximately 5 mg of the sample was placed in an aluminum non-sealed container and heated to 700°C at a heating rate of 10°C / min in a nitrogen gas (30 mL / min) stream. The temperature at which a thermal weight loss of 5% was observed was defined as the thermal decomposition temperature (Tg), and the heat resistance was evaluated according to the following criteria. Rating A: Thermal decomposition temperature is 350°C or higher Rating B: Thermal decomposition temperature is 300℃ or higher but less than 350℃ Rating C: Thermal decomposition temperature is less than 300℃

[0208] (Synthesis Example 1) Synthesis of R1-BisA-CN In a 300mL container equipped with a stirrer, a cooling tube, and a buret, 13.9g (50mmol) of biscyanatophenylpropane (hereinafter referred to as BisA-CN: manufactured by Mitsubishi Gas Chemical Co., Ltd.) and 50mL of 1,2-dichloroethane were charged and dissolved, and the slight amount of insoluble matter remaining was removed by filtration using a membrane filter (made of PTFE, pore size 0.45μm) to prepare a 1M solution. 3.5g (38mM) of phenol was added to this solution and stirred at 40℃ for 7 days. After cooling, 100mL of methanol was added, the resulting precipitate was filtered, and the collected matter was washed with methanol and dried under reduced pressure at 40℃ to obtain a phenol-containing triazine polymer (R1-BisA-CN) represented by the following formula in a yield of 52%. The polystyrene-equivalent molecular weight of the resulting resin was measured by the above-mentioned method, and the results were Mn: 5942, Mw: 8200, and Mw / Mn: 1.38. The obtained resinous prepolymer (hereinafter referred to as "resin") was subjected to the measurement under the above-mentioned conditions. 1 H-NMR, 13 When C-NMR measurement was performed, the following peaks were observed, and it was confirmed that the compound had at least the chemical structural unit of the following formula: 1 H-NMR; δ(ppm)9.7~9.8(OH), 7.0~7.9(Ph-H) 13 C-NMR; δ(ppm) 173 (triazine ring C), 155 (C-OH)

[0209] [ka]

[0210] (Synthesis Example 2) Synthesis of R2-BisA-CN A phenol-containing triazine polymer (R2-BisA-CN) represented by the following formula was obtained in a yield of 52% in the same manner as in Synthesis Example 1, except that 7.4 g (40 mM) of 4,4'-biphenol was used instead of phenol and the reaction conditions were 40°C and stirring for 5 days. The polystyrene-equivalent molecular weights of the resulting resin were measured by the above-mentioned method, and were found to be Mn: 5760, Mw: 7430, and Mw / Mn: 1.29. The analytical results of the obtained resin are as follows, and it was confirmed that the resin had at least the chemical structural unit of the following formula: 1 H-NMR; δ(ppm)9.5~9.6(OH), 6.9~7.9(Ph-H) 13 C-NMR; δ(ppm) 173 (triazine ring C), 155 (C-OH)

[0211] [ka]

[0212] (Synthesis Example 3) Synthesis of R1-DHPE-CN In a 300mL container equipped with a stirrer, a cooling tube, and a buret, 12.9g (50mmol) of biscyanate diphenyl ether (hereinafter referred to as DHPE-CN: manufactured by Mitsubishi Gas Chemical Co., Ltd.) and 50mL of 1,2-dichloroethane were charged and dissolved, and the slight amount of insoluble matter remaining was removed by filtration using a membrane filter (made of PTFE, pore size 0.45μm) to prepare a 1M solution. 3.5g (38mM) of phenol was added to this solution and stirred at 40℃ for 7 days. After cooling, 100mL of methanol was added, the resulting precipitate was filtered, and the collected matter was washed with methanol and dried under reduced pressure at 40℃ to obtain a phenol-containing triazine polymer (R1-DHPE-CN) represented by the following formula in a yield of 35%. The polystyrene-equivalent molecular weight of the resulting resin was measured by the above-mentioned method, and the results were Mn: 4128, Mw: 5493, and Mw / Mn: 1.33. When the obtained resin was subjected to NMR measurement under the above-mentioned measurement conditions, the following peaks were observed, and it was confirmed that the resin had at least the chemical structural unit of the following formula. 1 H-NMR; δ(ppm)9.4~9.5(OH), 6.9~7.7(Ph-H) 13C-NMR; δ(ppm) 172 (triazine ring C), 155 (C-OH)

[0213] [ka]

[0214] (Synthesis Example 4) Synthesis of R2-DHPE-CN A phenol-containing triazine polymer (R2-DHPE-CN) represented by the following formula was obtained in a yield of 47% in the same manner as in Synthesis Example 3, except that 7.4 g (40 mM) of 4,4'-biphenol was used instead of phenol. The polystyrene-equivalent molecular weight of the resulting resin was measured by the above-mentioned method, and the results were Mn: 4,500, Mw: 6,345, and Mw / Mn: 1.41. The analytical results of the obtained resin are as follows, and it was confirmed that the resin had at least the chemical structural unit of the following formula: 1 H-NMR; δ(ppm)9.2~9.3(OH), 6.9~7.6(Ph-H) 13 C-NMR; δ(ppm) 173 (triazine ring C), 155 (C-OH)

[0215] [ka]

[0216] (Synthesis Example 5) Synthesis of R1-TRP-CN In a 300mL container equipped with a stirrer, a cooling tube, and a buret, 18.9g (50mmol) of tricyanatophenylmethane (hereinafter referred to as TRP-CN: manufactured by Mitsubishi Gas Chemical Co., Ltd.) and 50mL of 1,2-dichloroethane were charged and dissolved, and the slight amount of insoluble matter remaining was removed by filtration using a membrane filter (made of PTFE, pore size 0.45μm) to prepare a 1M solution. 3.5g (38mM) of phenol was added to this solution and stirred at 40℃ for 6 days. After cooling, 100mL of methanol was added, the resulting precipitate was filtered, and the collected matter was washed with methanol and dried under reduced pressure at 40℃ to obtain a phenol-containing triazine polymer (R1-TRP-CN) represented by the following formula in a yield of 39%. The polystyrene-equivalent molecular weight of the resulting resin was measured by the above-mentioned method, and the results were Mn: 6978, Mw: 9630, and Mw / Mn: 1.38. The obtained resin was subjected to the above measurement conditions. 1 H-NMR, 13 When C-NMR measurement was performed, the following peaks were observed, and it was confirmed that the compound had at least the chemical structural unit of the following formula: 1 H-NMR; δ(ppm)9.4~9.5(OH), 6.8~7.9(Ph-H) 13 C-NMR; δ(ppm) 172 (triazine ring C), 154 (C-OH)

[0217] [ka]

[0218] (Synthesis Example 6) Synthesis of R2-TRP-CN A phenol-containing triazine polymer (R2-TRP-CN) represented by the following formula was obtained in a yield of 32% in the same manner as in Synthesis Example 5, except that 7.4 g (40 mM) of 4,4'-biphenol was used instead of phenol and the reaction conditions were 40°C and stirring for 5 days. The polystyrene-equivalent molecular weight of the resulting resin was measured by the above-mentioned method, and the results were Mn: 6630, Mw: 8620, and Mw / Mn: 1.30. The analytical results of the obtained resin are as follows, and it was confirmed that the resin had at least the chemical structural unit of the following formula: 1 H-NMR; δ(ppm)9.3~9.4(OH), 6.8~7.9(Ph-H) 13 C-NMR; δ(ppm) 172 (triazine ring C), 154 (C-OH)

[0219] [ka]

[0220] (Comparative Synthesis Example 1) A four-neck flask with a capacity of 10 L and a bottom-removable capacity equipped with a Dimroth condenser, a thermometer, and a stirring blade was prepared. 1.09 kg (7 mol, manufactured by Mitsubishi Gas Chemical Co., Ltd.) of 1,5-dimethylnaphthalene, 2.1 kg of 40 mass% formalin aqueous solution (28 mol as formaldehyde, manufactured by Mitsubishi Gas Chemical Co., Ltd.), and 0.97 mL of 98 mass% sulfuric acid (manufactured by Kanto Chemical Co., Ltd.) were charged into this four-neck flask in a nitrogen stream, and the mixture was reacted for 7 hours while refluxing at 100°C under normal pressure. Then, 1.8 kg of ethylbenzene (special grade reagent manufactured by Wako Pure Chemical Industries, Ltd.) was added as a dilution solvent to the reaction solution, and the reaction solution was allowed to stand, after which the aqueous phase in the lower phase was removed. Further, the mixture was neutralized and washed with water, and ethylbenzene and unreacted 1,5-dimethylnaphthalene were distilled off under reduced pressure to obtain 1.25 kg of dimethylnaphthalene formaldehyde resin as a light brown solid.

[0221] Next, a four-neck flask with an internal volume of 0.5 L equipped with a Dimroth condenser, a thermometer, and a stirring blade was prepared. In this four-neck flask, 100 g (0.51 mol) of the dimethylnaphthalene formaldehyde resin obtained as described above and 0.05 g of paratoluenesulfonic acid were charged under a nitrogen gas flow, and the temperature was raised to 190°C and heated for 2 hours, and then stirred. Then, 52.0 g (0.36 mol) of 1-naphthol was added, and the temperature was raised to 220°C and reacted for 2 hours. After dilution with a solvent, neutralization and washing with water were performed, and the solvent was removed under reduced pressure to obtain 126.1 g of a modified resin (CR-1) as a black-brown solid.

[0222] [Examples 1 to 6 and Comparative Example 1] The heat resistance of the resins obtained in Synthesis Examples 1 to 6 and Comparative Synthesis Example 1 was evaluated, and the results are shown in Table 1.

[0223] [Table 1]

[0224] As is clear from Table 1, it was confirmed that the resins used in Examples 1 to 6 have good heat resistance, but the compound used in Comparative Example 1 has poor heat resistance.

[0225] [Examples 7 to 12, Comparative Example 2] (Heat resistance and resist performance) The resins obtained in Synthesis Examples 1 to 6 were subjected to the following heat resistance test and resist performance evaluation. The results are shown in Table 2.

[0226] (Preparation of resist composition) Using each of the above resins, a resist composition was prepared according to the formulation shown in Table 2. Of the components of the resist composition in Table 2, the acid generator (C), acid diffusion controller (E) and solvent used were as follows. Acid Generator (C) P-1: Triphenylbenzenesulfonium trifluoromethanesulfonate (Midori Chemical Co., Ltd.) Acid diffusion control agent (E) Q-1: Trioctylamine (Tokyo Chemical Industry Co., Ltd.) solvent S-1: Propylene glycol monomethyl ether (Tokyo Chemical Industry Co., Ltd.)

[0227] (Method of Evaluating Resist Performance of Resist Composition) A uniform resist composition was spin-coated on a clean silicon wafer, and then pre-exposure baked (PB) in an oven at 110°C to form a resist film with a thickness of 60 nm. The obtained resist film was irradiated with an electron beam in a 1:1 line-and-space setting with a 50 nm interval using an electron beam lithography device (ELS-7500, manufactured by Elionix Co., Ltd.). After the irradiation, the resist film was heated at a predetermined temperature for 90 seconds, and developed by immersing in an alkaline developer containing 2.38 mass% tetramethylammonium hydroxide (TMAH) for 60 seconds. Thereafter, the resist film was washed with ultrapure water for 30 seconds and dried to form a positive resist pattern. The lines and spaces of the formed resist pattern were observed using a scanning electron microscope (S-4800, manufactured by Hitachi High-Technologies Co., Ltd.) to evaluate the reactivity of the resist composition due to electron beam irradiation.

[0228] [Table 2]

[0229] Regarding the evaluation of the resist pattern, in Examples 7 to 12, a good resist pattern was obtained by irradiating an electron beam with a 1:1 line and space setting with a 50 nm interval. The line edge roughness was determined to be good when the unevenness of the pattern was less than 50 nm. On the other hand, in Comparative Example 2, a good resist pattern could not be obtained.

[0230] In this way, when the prepolymer (resin) of the present invention was used, the heat resistance was higher and a good resist pattern shape was obtained, compared to the resin (CR-1) of Comparative Example 2, which did not satisfy the requirements. As long as the requirements of the present invention are satisfied, similar effects can be obtained with resins other than those described in the examples.

[0231] [Examples 13 to 18, Comparative Example 3] (Preparation of Radiation-Sensitive Composition) The components shown in Table 3 were mixed to prepare a homogeneous solution, and then the homogeneous solution was filtered through a Teflon (registered trademark) membrane filter having a pore size of 0.1 μm to prepare a radiation-sensitive composition. Each of the prepared radiation-sensitive compositions was evaluated as follows.

[0232] [Table 3]

[0233] In Comparative Example 3, the following resist base material was used. PHS-1: Polyhydroxystyrene Mw=8000 (Sigma-Aldrich) As the photoactive compound (B), the following was used. B-1: A naphthoquinone diazide photosensitizer having the following chemical structural formula (G) (4NT-300, Toyo Gosei Co., Ltd.) Furthermore, the following solvents were used: S-1: Propylene glycol monomethyl ether (Tokyo Chemical Industry Co., Ltd.)

[0234] [ka]

[0235] (Evaluation of Resist Performance of Radiation-Sensitive Composition) The radiation-sensitive composition obtained above was spin-coated on a clean silicon wafer, and then pre-exposure baked (PB) in an oven at 110°C to form a resist film with a thickness of 200 nm. The resist film was exposed to ultraviolet light using an ultraviolet exposure device (Mikasa mask aligner MA-10). The ultraviolet lamp used was an ultra-high pressure mercury lamp (relative intensity ratio of g-line: h-line: i-line: j-line = 100: 80: 90: 60). After irradiation, the resist film was heated at 110°C for 90 seconds, and developed by immersing in an alkaline developer containing 2.38% by mass of TMAH for 60 seconds. The resist film was then washed with ultra-pure water for 30 seconds and dried to form a 5 μm positive resist pattern.

[0236] The lines and spaces obtained in the formed resist pattern were observed with a scanning electron microscope (S-4800, manufactured by Hitachi High-Technologies Corp.) Line edge roughness was considered good when the unevenness of the pattern was less than 50 nm.

[0237] When the radiation-sensitive compositions of Examples 13 to 18 were used, resist patterns with a good resolution of 5 μm were obtained. Furthermore, the pattern roughness was also small and good.

[0238] On the other hand, when the radiation-sensitive composition of Comparative Example 3 was used, a good resist pattern with a resolution of 5 μm was obtained, but the roughness of the pattern was significantly poor.

[0239] As described above, it was found that the radiation-sensitive compositions of Examples 13 to 18 were capable of forming resist patterns with less roughness and a good shape, compared to the radiation-sensitive composition of Comparative Example 3. As long as the above-mentioned requirements of the present invention are satisfied, radiation-sensitive compositions other than those described in the examples also exhibit the same effects.

[0240] Furthermore, since the resins obtained in Synthesis Examples 1 to 6 have a relatively low molecular weight and low viscosity, it was evaluated that the materials for forming underlayer films for lithography using these resins can relatively advantageously improve the embedding characteristics and the flatness of the film surface. In addition, since the thermal decomposition temperatures of all of them are 350°C or higher (evaluation A) and they have high heat resistance, it was evaluated that they can be used even under high temperature baking conditions. In order to confirm these points, the following evaluation was carried out assuming the use of underlayer films.

[0241] [Examples 19-1 to 24-2, Comparative Example 4] (Preparation of composition for forming underlayer film for lithography) Compositions for forming an underlayer film for lithography were prepared so as to have the compositions shown in Table 4. Next, these compositions for forming an underlayer film for lithography were spin-coated onto a silicon substrate, and then baked at 240° C. for 60 seconds and then at 400° C. for 120 seconds to prepare underlayer films with a thickness of 200 nm. The acid generators, crosslinking agents, and organic solvents used were as follows. Acid generator: Di-t-Bt diphenyliodonium nonafluoromethanesulfonate (DTDPI) manufactured by Midori Chemical Co., Ltd. Crosslinking agent: Nikalac MX270 (Nikalac) manufactured by Sanwa Chemical Co., Ltd. Organic solvent: Cyclopentanone (CPN) Novolak: Gun-ei Chemical Co., Ltd. PSM4357

[0242] Next, an etching test was carried out under the conditions shown below to evaluate the etching resistance. The evaluation results are shown in Table 4.

[0243] [Etching test] Etching equipment: Samco International RIE-10NR Output: 50W Pressure: 20Pa Time: 2 minutes Etching Gas Ar gas flow rate: CF4 gas flow rate: O2 gas flow rate = 50:5:5 (sccm)

[0244] (Evaluation of Etching Resistance) The etching resistance was evaluated by the following procedure. First, a novolac underlayer film was prepared under the same conditions as above, except that novolac (PSM4357 manufactured by Gun-ei Chemical Co., Ltd.) was used. The above etching test was performed on this novolac underlayer film, and the etching rate was measured.

[0245] Next, the underlayer films of Examples 19-1 to 24-2 and Comparative Example 4 were prepared under the same conditions as the underlayer film of the novolac, and the above-mentioned etching test was carried out in the same manner to measure the etching rate. The etching resistance was evaluated according to the following evaluation criteria, based on the etching rate of the underlayer film of the novolac. [Evaluation Criteria] A: Etching rate is less than -20% compared to the novolac underlayer. B: The etching rate is -20% to 0% compared to the underlayer of novolac. C: Etching rate is more than +0% compared to the underlayer of novolac

[0246] [Table 4]

[0247] It was found that Examples 19-1 to 24-2 exhibited superior etching rates compared to the underlayer film of novolac and the underlayer film of Comparative Example 4. On the other hand, it was found that the underlayer film of Comparative Example 4 exhibited an etching rate inferior to that of the underlayer film of novolac.

[0248] [Examples 25-1 to 30-2, Comparative Example 5] Next, the composition for forming an underlayer film for lithography used in Examples 19-1 to 24-2 and Comparative Example 4 was applied to a SiO2 substrate with a thickness of 80 nm and 60 nm lines and spaces, and baked at 240°C for 60 seconds to form a 90 nm underlayer film.

[0249] (Evaluation of embeddability) The embeddability was evaluated by the following procedure. Specifically, a cross section of the film obtained under the above conditions was cut out and observed under an electron microscope to evaluate the embeddability. The evaluation results are shown in Table 5.

[0250] [Evaluation Criteria] A: The underlayer film is embedded without any defects in the uneven parts of the 60 nm line and space SiO2 substrate. C: There is a defect in the uneven portion of the 60 nm line and space SiO2 substrate, and the underlayer film is not filled in.

[0251] [Table 5]

[0252] It was found that the embedding properties were good in Examples 25-1 to 30-2, whereas in Comparative Example 5, defects were observed in the uneven portions of the SiO2 substrate, and it was found that the embedding properties were poor.

[0253] [Examples 31-1 to 36-2] Next, the composition for forming an underlayer film for lithography used in Examples 19-1 to 24-2 was applied onto a SiO2 substrate having a thickness of 300 nm, and baked at 240° C. for 60 seconds and then at 400° C. for 120 seconds to form an underlayer film having a thickness of 85 nm. An ArF resist solution was applied onto this underlayer film, and baked at 130° C. for 60 seconds to form a photoresist layer having a thickness of 140 nm.

[0254] The ArF resist solution used was prepared by mixing 5 parts by mass of a compound of the following formula (16), 1 part by mass of triphenylsulfonium nonafluoromethanesulfonate, 2 parts by mass of tributylamine, and 92 parts by mass of PGMEA.

[0255] The compound of the following formula (16) was prepared as follows. That is, 4.15 g of 2-methyl-2-methacryloyloxyadamantane, 3.00 g of methacryloyloxy-γ-butyrolactone, 2.08 g of 3-hydroxy-1-adamantyl methacrylate, and 0.38 g of azobisisobutyronitrile were dissolved in 80 mL of tetrahydrofuran to obtain a reaction solution. The reaction solution was polymerized for 22 hours under a nitrogen atmosphere at a reaction temperature of 63° C., and then the reaction solution was dropped into 400 mL of n-hexane. The resin thus produced was coagulated and purified, and the white powder thus produced was filtered and dried overnight at 40° C. under reduced pressure to obtain a compound represented by the following formula (16).

[0256] [ka]

[0257] In the formula (16), 40, 40, and 20 indicate the ratio of each constituent unit, and do not indicate that it is a block copolymer.

[0258] Next, the photoresist layer was exposed to light using an electron beam lithography system (ELS-7500, 50 keV, manufactured by Elionix), baked (PEB) at 115°C for 90 seconds, and developed with a 2.38 mass% aqueous solution of tetramethylammonium hydroxide (TMAH) for 60 seconds to obtain a positive resist pattern.

[0259] [Comparative Example 6] A photoresist layer was formed directly on a SiO2 substrate in the same manner as in Example 31-1, except that no underlayer film was formed, to obtain a positive resist pattern.

[0260] [evaluation] For each of Examples 31-1 to 36-2 and Comparative Example 6, the shapes of the obtained resist patterns of 45 nmL / S (1:1) and 80 nmL / S (1:1) were observed using an electron microscope (S-4800) manufactured by Hitachi, Ltd. Regarding the shape of the resist pattern after development, those without pattern collapse and with good rectangularity were evaluated as good, and those without were evaluated as bad. Furthermore, as a result of the observation, the minimum line width without pattern collapse and with good rectangularity was used as an index of evaluation as resolution. Furthermore, the minimum amount of electron beam energy capable of drawing a good pattern shape was used as an index of evaluation as sensitivity. The results are shown in Table 6.

[0261] [Table 6]

[0262] As is clear from Table 6, it was confirmed that the resist patterns in Examples 31-1 to 36-2 were significantly superior in both resolution and sensitivity to those in Comparative Example 6. In addition, it was confirmed that the resist pattern shape after development was free of pattern collapse and had good rectangularity. Furthermore, the difference in the resist pattern shape after development showed that the underlayer film forming materials for lithography in Examples 31-1 to 36-2 had good adhesion to the resist material.

[0263] [Example 37] The composition for forming an underlayer film for lithography used in Example 19-1 was applied onto a SiO2 substrate with a thickness of 300 nm, and baked at 240°C for 60 seconds and then at 400°C for 120 seconds to form an underlayer film with a thickness of 90 nm. A silicon-containing intermediate layer material was applied onto this underlayer film, and baked at 200°C for 60 seconds to form an intermediate layer film with a thickness of 35 nm. Furthermore, the ArF resist solution was applied onto this intermediate layer film, and baked at 130°C for 60 seconds to form a photoresist layer with a thickness of 150 nm. As the silicon-containing intermediate layer material, a silicon atom-containing polymer described in <Synthesis Example 1> of JP2007-226170A was used.

[0264] Next, the photoresist layer was exposed to light through a mask using an electron beam lithography system (ELS-7500, 50 keV, manufactured by Elionix), baked at 115°C for 90 seconds (PEB), and developed with a 2.38 mass% aqueous solution of tetramethylammonium hydroxide (TMAH) for 60 seconds to obtain a positive resist pattern of 45 nmL / S (1:1).

[0265] Then, using a Samco International RIE-10NR, the silicon-containing intermediate layer film (SOG) was dry etched using the obtained resist pattern as a mask, followed by dry etching of the underlayer film using the obtained silicon-containing intermediate layer film pattern as a mask, and then dry etching of the SiO2 film using the obtained underlayer film pattern as a mask.

[0266] The etching conditions for each are as follows. [Etching conditions for resist pattern onto resist middle layer film] Output: 50W Pressure: 20Pa Time: 1 min Etching Gas Ar gas flow rate: CF4 gas flow rate: O2 gas flow rate = 50:8:2 (sccm) [Etching conditions for resist intermediate film pattern onto resist underlayer film] Output: 50W Pressure: 20Pa Time: 2 minutes Etching Gas Ar gas flow rate: CF4 gas flow rate: O2 gas flow rate = 50:5:5 (sccm) [Etching conditions for resist underlayer film pattern onto SiO2 film] Output: 50W Pressure: 20Pa Time: 2 minutes Etching Gas Ar gas flow rate: C5F 12 Gas flow rate: C2F6 gas flow rate: O2 gas flow rate =50:4:3:1(sccm)

[0267] [evaluation] The cross section of the pattern of Example 37 obtained as described above (shape of the SiO2 film after etching) was observed using an electron microscope (S-4800) manufactured by Hitachi, Ltd. It was confirmed that in the example using the underlayer film of the present invention, the shape of the SiO2 film after etching in the multilayer resist processing was rectangular, and no defects were observed, which was good.

[0268] [Examples 38 to 43, Comparative Example 7] An optical component forming composition having the same composition as the solution of the underlayer film forming material for lithography prepared in each of the above Examples 19-1 to 24-2 and Comparative Example 5 was applied onto a SiO2 substrate with a thickness of 300 nm, and baked at 260°C for 300 seconds to form a film for optical components with a thickness of 100 nm. Next, a refractive index and transparency test was performed at a wavelength of 633 nm using a vacuum ultraviolet multi-angle spectroscopic ellipsometer (VUV-VASE) manufactured by J.A. Woollam Japan, and the refractive index and transparency were evaluated according to the following criteria. The evaluation results are shown in Table 7.

[0269] [Refractive index evaluation criteria] A: Refractive index is 1.65 or more C: Refractive index less than 1.65

[0270] [Transparency evaluation criteria] A: Extinction coefficient less than 0.03 C: Extinction coefficient is 0.03 or more

[0271] [Table 7]

[0272] It was found that the optical part forming compositions of Examples 38-1 to 43-2 not only had a high refractive index but also a low absorption coefficient and excellent transparency, whereas the composition of Comparative Example 7 was found to have poor performance as an optical part.

[0273] [Example 44] Acid purification of R1-BisA-CN In a 1000 mL four-neck flask (bottom-opening type), 150 g of the solution (10 mass%) obtained in Synthesis Example 1 dissolved in cyclohexanone was charged and heated to 80 ° C. with stirring. Next, 37.5 g of an aqueous oxalic acid solution (pH 1.3) was added, stirred for 5 minutes, and then allowed to stand for 30 minutes. As a result, the oil phase and the aqueous phase were separated, and the aqueous phase was removed. After repeating this operation once, 37.5 g of ultrapure water was charged into the obtained oil phase, stirred for 5 minutes, and then allowed to stand for 30 minutes, and the aqueous phase was removed. After repeating this operation three times, the flask was heated to 80 ° C. while reducing the pressure inside to 200 hPa or less, and the residual water and cyclohexanone were concentrated and distilled off. Thereafter, EL grade cyclohexanone (a reagent manufactured by Kanto Chemical Co., Ltd.) was diluted and the concentration was adjusted to 10 mass %, thereby obtaining a cyclohexanone solution of R1-BisA-CN with a reduced metal content.

[0274] [Comparative Example 8] Purification of R1-BisA-CN with ultrapure water The same procedure as in Example 44 was carried out except that ultrapure water was used instead of the aqueous oxalic acid solution, and the concentration was adjusted to 10 mass %, thereby obtaining a cyclohexanone solution of R1-BisA-CN.

[0275] The contents of various metals were measured by ICP-MS for the 10 mass % cyclohexanone solution of R1-BisA-CN before treatment and for the solutions obtained in Example 44 and Comparative Example 8. The measurement results are shown in Table 8.

[0276] [Table 8]

[0277] <Example B1-1> The composition for forming an underlayer film for lithography prepared in Example 19-1 was spin-coated on a silicon substrate and baked at 150° C. for 60 seconds to form a film and remove the solvent. Then, a high-temperature heat resistance evaluation was performed using a lamp annealing furnace as described below.

[0278] <Examples B1-2 to B6-2, Comparative Examples B1 to B2> Except for changing the composition for forming an underlayer film for lithography used to the composition shown in Table 9, the high-temperature heat resistance evaluation was carried out in the same manner as in Example B1-1.

[0279] [High temperature heat resistance evaluation of cured film] The substrate on which the film was formed was heated at 450°C in a nitrogen atmosphere, and the film thickness change rate was determined for 4 and 10 minutes after the start of heating. Heating was continued at 550°C in a nitrogen atmosphere, and the film thickness change rate was determined for 4 and 10 minutes after the start of heating. These film thickness change rates were evaluated as an index of the heat resistance of the cured film. The film thickness before and after the heat resistance test was measured with an interference film thickness meter, and the film thickness change rate (percentage %) based on the film thickness before the heat resistance test treatment was taken as the film thickness variation value. The results are shown in Table 9. In the table, positive values ​​indicate that the film has shrunk.

[0280] [Table 9]

[0281] <Example C1> A 12-inch silicon wafer was subjected to thermal oxidation treatment to prepare a substrate having a silicon oxide film, and a resin film having a thickness of 100 nm was formed thereon in the same manner using the composition for forming a film for lithography of Example 19-1. A silicon oxide film and a SiN film were formed on the resin film as described below, and the PE-CVD film forming properties were evaluated.

[0282] <Examples C1-2 to C6-2 and Comparative Examples C1 to C2> A film was formed in the same manner as in Example C1-1, except that the film-forming composition for lithography used was changed to the composition shown in Table 10, and then the film was evaluated.

[0283] [Silicon oxide film evaluation] A silicon oxide film with a thickness of 70 nm was formed on the resin film using a film forming device TELINDY (manufactured by Tokyo Electron Ltd.) and TEOS (tetraethylsiloxane) as a raw material at a substrate temperature of 300° C. A defect inspection was performed on the wafer with the cured film laminated with this silicon oxide film using a KLA-Tencor SP-5, and the number of defects in the formed oxide film was evaluated using the number of defects of 21 nm or more as an index. A Number of defects ≦ 20 B 20 pieces < Number of defects ≦ 50 pieces C 50 pieces < Number of defects ≦ 100 pieces D 100 pieces < Number of defects ≦ 1000 pieces E 1000 pieces < Number of defects ≦ 5000 pieces F 5000 pieces < Number of defects

[0284] [SiN film evaluation] Using the same method as above, a hardened film was formed on a substrate having a silicon oxide film of 100 nm thickness formed by thermal oxidation on a 12-inch silicon wafer, and then a film-forming device TELINDY (manufactured by Tokyo Electron Ltd.) was used to form a SiN film with a thickness of 40 nm, a refractive index of 1.94, and a film stress of -54 MPa at a substrate temperature of 350°C using SiN4 (monosilane) and ammonia as raw materials. The wafer with the hardened film laminated with the SiN film was subjected to defect inspection using KLA-Tencor SP-5, and the number of defects in the formed oxide film was evaluated using the number of defects of 21 nm or more as an index as described above. These results are shown in Table 10.

[0285] [Table 10]

[0286] The silicon oxide films or SiN films formed on the resin films of Examples C1-1 to C6-2 had 50 or less defects measuring 21 nm or more (rating B or higher), which was shown to be less than the number of defects in Comparative Examples C1 and C2.

[0287] <Example D1-1> A 12-inch silicon wafer was subjected to thermal oxidation treatment to form a silicon oxide film, and a resin film was formed to a thickness of 100 nm on the substrate using the lithography film-forming composition solution obtained in Example 19-1 in the same manner as in Example C1-1. The resin film was further subjected to annealing treatment by heating at 600°C for 4 minutes using a hot plate capable of high-temperature treatment in a nitrogen atmosphere, to produce a wafer on which an annealed resin film was laminated. The substrate was subjected to an etching evaluation as described below.

[0288] [Etching evaluation after high-temperature treatment] The substrate was etched using a TELIUS etching device (Tokyo Electron) under the conditions of using CF4 / Ar and Cl2 / Ar as etching gases, and the etching rate was evaluated. The etching rate was evaluated by using a 200 nm thick resin film prepared by annealing SU8 (Nippon Kayaku) at 250°C for 1 minute as a reference, and calculating the speed ratio of the etching rate to SU8 as a relative value.

[0289] <Examples D1-2 to D6-2, Comparative Examples D1 to D2> Except for changing the film-forming composition for lithography used to the composition shown in Table 11, the etching evaluation after the high-temperature treatment was carried out in the same manner as in Example D1-1.

[0290] [Table 11] [Industrial Applicability]

[0291] The prepolymer of the present invention has high heat resistance and high solvent solubility, and is applicable to wet processes. Therefore, the lithography film-forming material using the prepolymer of the present invention and the lithography film thereof can be widely and effectively used in various applications requiring these performances. Therefore, the present invention can be widely and effectively used in, for example, electrical insulating materials, resist resins, semiconductor sealing resins, printed wiring board adhesives, electrical laminates mounted on electrical equipment, electronic equipment, industrial equipment, etc., matrix resins for prepregs mounted on electrical equipment, electronic equipment, industrial equipment, etc., build-up laminate materials, resins for fiber reinforced plastics, sealing resins for liquid crystal display panels, paints, various coating agents, adhesives, coating agents for semiconductors, resist resins for semiconductors, resins for forming underlayer films, etc. In particular, the present invention can be effectively used in the field of lithography films.

Claims

1. A prepolymer having a triazine skeleton obtained by reacting a polyfunctional cyanate compound with a phenol, The polyfunctional cyanate compound is represented by formula (1-1) or formula (2-1), The phenol is represented by formula (4), The mass average molecular weight is 5493 to 10000. Prepolymer for film-forming materials for lithography. 【Chemistry 1】 (In formula (1-1) and formula (2-1), R 2 represents a single bond or a divalent group having 0 to 40 carbon atoms which may contain a heteroatom, R 3 is a trivalent group having 0 to 40 carbon atoms which may contain a heteroatom, R 0 each independently represents an alkyl group having 1 to 40 carbon atoms which may have a substituent, an aryl group having 6 to 40 carbon atoms which may have a substituent, an alkenyl group having 2 to 40 carbon atoms which may have a substituent, an alkynyl group having 2 to 40 carbon atoms which may have a substituent, an alkoxy group having 1 to 40 carbon atoms which may have a substituent, or an aryloxy group having 6 to 40 carbon atoms which may have a substituent, Each m' is independently an integer from 0 to 8; Each p is independently an integer of 0 to 3. 【Chemistry 2】 In formula (4), Z is a single bond, a heteroatom, or a divalent hydrocarbon group having 1 to 40 carbon atoms which may contain a heteroatom; each R 1 independently represents an alkyl group having 1 to 40 carbon atoms which may have a substituent, an aryl group having 6 to 40 carbon atoms which may have a substituent, an alkenyl group having 2 to 40 carbon atoms which may have a substituent, an alkoxy group having 1 to 40 carbon atoms which may have a substituent, a halogen atom, or a hydroxyl group, with the proviso that at least one R 1 is a hydroxyl group; Each e is independently an integer from 1 to 9; Each f is independently an integer from 0 to 3; n is an integer from 0 to 3.

2. The prepolymer according to claim 1, wherein the phenol represented by the formula (4) is a monophenol represented by the following formula (4-1): 【Chemistry 3】 (In formula (4-1), R 1 , e, and f are defined as above, except that the number of hydroxyl groups is one.

3. The prepolymer according to claim 1 or 2, which has a phenolic hydroxyl group at its terminal.

4. A film-forming composition for lithography, comprising the prepolymer according to any one of claims 1 to 3.

5. The film-forming composition for lithography according to claim 4 , further comprising a solvent.

6. A resist film formed from the composition according to claim 4 or 5.

7. forming a resist film on a substrate using the film-forming composition for lithography according to claim 4 or 5; exposing at least a portion of the formed resist film; developing the exposed resist film to form a resist pattern; A method for forming a resist pattern comprising the steps of:

8. A film-forming composition for lithography, comprising the prepolymer according to any one of claims 1 to 3, a diazonaphthoquinone photoactive compound, and a solvent, The film-forming composition for lithography, wherein the content of the solvent in the composition is 20 to 99 mass %.

9. When the components other than the solvent are considered to be solid contents, the solid contents are 1 to 99% by weight of the prepolymer; 99 to 1% by weight of the diazonaphthoquinone photoactive compound; The film-forming composition for lithography according to claim 8, further comprising 0 to 49% by mass of other optional components.

10. 10. An amorphous film obtained by spin coating the film-forming composition for lithography according to claim 4.

11. A method for producing an amorphous film, comprising the step of forming an amorphous film on a substrate using the film-forming composition for lithography according to claim 4 .

12. forming a resist film on a substrate using the film-forming composition for lithography according to claim 4; exposing at least a portion of the formed resist film; developing the exposed resist film to form a resist pattern.

13. An underlayer film for lithography formed from the film-forming composition for lithography according to claim 4 .

14. A method for producing an underlayer film for lithography, comprising the step of forming an underlayer film on a substrate using the film-forming composition for lithography according to claim 4 .

15. A process for forming an underlayer film on a substrate using the film-forming composition for lithography according to any one of claims 4, 5, 8, and 9; forming at least one photoresist layer on the underlayer film; irradiating predetermined areas of the photoresist layer with radiation and developing the photoresist layer to form a resist pattern; The method for forming a resist pattern comprises the steps of:

16. A step of forming an underlayer film on a substrate using the film-forming composition for lithography according to any one of claims 4, 5, 8, and 9; forming an intermediate layer film on the underlayer film using a resist intermediate layer film material containing silicon atoms; forming at least one photoresist layer on the intermediate layer film; irradiating predetermined areas of the photoresist layer with radiation and developing the photoresist layer to form a resist pattern; a step of etching the intermediate layer film using the resist pattern as a mask to form an intermediate layer film pattern; forming an underlayer film pattern by etching the underlayer film using the intermediate layer film pattern as an etching mask; Etching the substrate using the underlayer film pattern as an etching mask to form a pattern on the substrate; The pattern forming method comprises the steps of:

Citation Information

Patent Citations

  • Method of manufacturing phenol modified cyanate oligomer composition, phenol modified cyanate oligomer composition to be obtained by its method, and prepreg and metal clad laminated sheet using its composition

    JP2001181388A

  • Thermosetting resin composition and prepreg, metal-clad laminate, and printed wiring board using the same

    JP2001240723A

  • Resist composition

    JP2005326838A

  • Radiation-sensitive resist composition

    JP2008145539A

  • Radiation-sensitive composition

    JP2009173623A